Silicon-carbon mixture, method for preparing same, and negative electrode active material and lithium secondary battery comprising same

By using silicon-carbon mixture in lithium secondary batteries to control the molar ratio of oxygen atoms to silicon, the problem of volume expansion of silicon-based negative electrode material in lithium secondary batteries is solved, the capacity retention rate and reliability of the battery are improved, and Simplified production process.

CN119213580APending Publication Date: 2024-12-27DAEJOO ELECTRONICS MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380041158.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-25
Filing Date
2023-03-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In existing lithium secondary batteries, the silicon-based negative electrode active material has a volume expansion of up to 300% during charging and discharging, resulting in material damage and electrical separation, reducing the capacity retention rate and reliability of the battery.

Method used

A silicon-carbon mixture is used to include silicon particles, magnesium silicate and carbon, and control the molar ratio of oxygen atoms to silicon in the range of 0.06 to 0.90 to form a composite material for preparing negative electrode active material by adjusting the composite material The structural and physical properties of lithium secondary batteries are optimized.

Benefits of technology

The excellent discharge capacity, initial efficiency and capacity retention rate of lithium secondary batteries are achieved, the reliability of the battery is improved, and large-scale production is achieved through simplified processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213580A_ABST
    Figure CN119213580A_ABST
Patent Text Reader

Abstract

The present invention relates to a silicon-carbon mixture, a method for preparing the same, and a negative electrode active material and a lithium secondary battery comprising the same. The silicon-carbon mixture includes two or more composite materials including silicon particles, magnesium silicate, and carbon, and a molar ratio of oxygen (O) atoms to silicon (Si) atoms satisfies 0.06 to 0.90. Accordingly, when the silicon-carbon mixture is applied to the negative electrode active material, it is possible to simultaneously improve the discharge capacity, initial efficiency, and capacity retention after circulation of the lithium secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-carbon mixture, a preparation method thereof, and a negative electrode active material and a lithium secondary battery containing the same. Background Art

[0002] In recent years, with the development of the information and communication industry, electronic devices have become smaller, lighter, thinner and more portable, and the demand for high-energy density batteries used as power sources for these electronic devices has increased. Lithium secondary batteries are the batteries that best meet this demand, and research is being actively conducted on small batteries using lithium secondary batteries and their application to large electronic devices such as automobiles and energy storage systems.

[0003] Carbon materials are widely used as negative electrode active materials for such lithium secondary batteries. In order to further increase the capacity of the battery, silicon-based negative electrode active materials are being studied. Since the theoretical capacity of silicon (4199 mAh / g) is 10 times or more greater than that of graphite (372 mAh / g), it is expected that the battery capacity will be significantly improved.

[0004] For example, the reaction when lithium is intercalated into silicon is as follows:

[0005] [Reaction formula 1]

[0006] 22Li+5Si=Li 22 Si5

[0007] In the silicon-based negative electrode active material according to the above reaction formula, an alloy with high capacity containing up to 4.4 lithium atoms per silicon atom is formed. However, in most silicon-based negative electrode active materials, the volume expansion of up to 300% due to the insertion of lithium damages the negative electrode, making it difficult to exhibit high cycle characteristics.

[0008] In addition, this volume change may cause cracks on the surface of the negative electrode active material, and ionic materials may be formed in the negative electrode active material, resulting in electrical separation of the negative electrode active material from the current collector. This electrical separation phenomenon can significantly reduce the capacity retention rate of the battery.

[0009] To solve this problem, Japanese Patent No. 4393610 discloses a negative electrode active material in which silicon and carbon are mechanically processed to form a composite material, and a carbon layer is coated on the surface of silicon particles using a chemical vapor deposition (CVD) method.

[0010] Furthermore, Japanese Laid-Open Patent Publication No. 2016-502253 discloses a negative electrode active material including porous silicon-based particles and carbon particles, wherein the carbon particles include fine carbon particles and coarse carbon particles having different average particle diameters.

[0011] However, although these prior art documents relate to negative electrode active materials containing silicon and carbon, they have limitations in suppressing volume expansion and contraction during charge and discharge. There may be a problem that the capacity retention rate will significantly decrease after a long period of thousands or more cycles, thereby reducing reliability.

[0012] [Prior art literature]

[0013] [Patent Document]

[0014] (Patent Document 1) Japanese Patent No. 4393610

[0015] (Patent Document 2) Japanese Laid-Open Patent Publication No. 2016-502253

[0016] (Patent Document 3) Korean Laid-Open Patent Publication No. 2018-0106485. Summary of the invention

[0017] Technical issues

[0018] The object of the present invention is to provide a silicon-carbon mixture, which includes two or more types of composite materials, including silicon particles, magnesium silicate and carbon, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms is controlled within a specific range, so that when the silicon-carbon mixture is applied to a negative electrode active material, the performance of a lithium secondary battery can be improved.

[0019] Another object of the present invention is to provide a method for preparing a silicon-carbon mixture.

[0020] Still another object of the present invention is to provide a negative electrode active material comprising the silicon-carbon mixture and a lithium secondary battery comprising the negative electrode active material.

[0021] Solution to the problem

[0022] In order to achieve the above-mentioned purpose, an embodiment of the present invention provides a silicon-carbon mixture, which includes two or more types of composite materials, including silicon particles, magnesium silicate and carbon, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms is 0.06 to 0.90.

[0023] Another embodiment provides a method for preparing a silicon-carbon mixture, the method comprising: a first step of obtaining a first composite material; a second step of obtaining a second composite material; and a third step of mixing the first composite material and the second composite material, wherein the first composite material comprises first silicon particles and first carbon, and the second composite material comprises second silicon particles, magnesium silicate, and second carbon.

[0024] Still another embodiment provides a negative electrode active material including the silicon-carbon mixture.

[0025] Further, another embodiment provides a lithium secondary battery including the negative electrode active material.

[0026] Advantageous Effects of the Invention

[0027] According to an embodiment, a silicon-carbon mixture is provided, which includes two or more types of composite materials, including silicon particles, magnesium silicate and carbon, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms is controlled within a specific range; therefore, a lithium secondary battery with balanced performance of excellent discharge capacity, initial efficiency and capacity retention rate after cycling can be obtained.

[0028] In particular, since the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture is controlled within a specific range, the carbon content and porosity can be easily controlled. Therefore, even after thousands or more cycles over a long period of time, excellent capacity retention can be maintained, thereby further improving reliability.

[0029] Furthermore, the method according to the embodiment has an advantage in that large-scale production can be performed through a continuous process with a minimum number of steps. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The following drawings attached to this specification illustrate preferred embodiments of the present invention and are used together with the description of the present invention to further understand the technical concept of the present invention. Therefore, the present invention should not be interpreted as being limited to those described in the drawings.

[0031] Figure 1 The results of analyzing the crystal structure of the silicon-carbon mixture prepared in Example 1 using an X-ray diffraction analyzer (X'Pert3 from Malvern Panalytical) are shown.

[0032] Figure 2 The results of analyzing the crystal structure of the silicon-carbon mixture obtained in Example 7 using an X-ray diffraction analyzer (X'Pert3 from Malvern Panalytical) are shown.

[0033] Figure 3 This is a FIB-SEM photograph of the porous silicon composite material prepared in Preparation Example 2-1 observed after magnification of 10,000 times.

[0034] Figure 4This is a FIB-SEM photograph of the porous silicon composite material prepared in Preparation Example 2-1 observed at a magnification of 30,000 times.

[0035] Figure 5 This is a FIB-SEM photograph of the porous silicon composite material prepared in Preparation Example 2-1 observed after magnification of 100,000 times.

[0036] Figure 6 This is a scanning electron microscope (FE-SEM) photograph of the first composite material prepared in Preparation Example 3-1 observed after magnification of 10,000 times.

[0037] Figure 7 This is a photograph of a bright field image of the first composite material prepared in Preparation Example 3-1 using a transmission electron microscope (FE-TEM).

[0038] Figure 8 The dark field image and bright field image of the first composite material prepared in Preparation Example 3-1 were taken using a transmission electron microscope (FE-TEM). DETAILED DESCRIPTION

[0039] Best Mode for Carrying Out the Invention

[0040] The present invention is not limited to the contents disclosed below. Instead, it can be modified in various forms as long as the gist of the present invention is not changed.

[0041] In the present specification, unless otherwise specified, when a part is referred to as “comprising” a certain element, it should be understood that the part may also include other elements.

[0042] Furthermore, unless otherwise indicated, all numbers and expressions relating to amounts of components, reaction conditions, and so forth used herein are to be understood as being modified by the term "about."

[0043] [Silicon Carbon Mixture]

[0044] The silicon-carbon mixture according to the embodiment includes two or more types of composite materials including silicon particles, magnesium silicate, and carbon, and a molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms is 0.06 to 0.90.

[0045] Since the silicon-carbon mixture according to the embodiment includes two or more types of composite materials, including silicon particles, magnesium silicate and carbon, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms is controlled within a specific range, a silicon-carbon mixture having a desired structure and physical properties can be obtained, and when the silicon-carbon mixture is applied to the negative electrode active material of a lithium secondary battery, the discharge capacity, initial efficiency and capacity retention rate after cycling of the lithium secondary battery can be simultaneously improved.

[0046] The molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture may be preferably 0.09 to 0.80, more preferably 0.09 to 0.60, even more preferably 0.10 to less than 0.60, and most preferably 0.1 to 0.50. When a silicon-carbon mixture satisfying the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the above silicon-carbon mixture is applied to a negative electrode active material, the content of silicon particles as an active material can be increased, thereby simultaneously improving the capacity retention rate, discharge capacity and initial efficiency of the lithium secondary battery. In particular, if the pore structure and porosity are controlled, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture is controlled within a specific range, even after a long period of thousands or more cycles, an excellent capacity retention rate can be maintained, thereby having a significant advantage in improving reliability.

[0047] If the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture is less than the above range, the manufacture of the silicon-carbon mixture is not easy due to process problems. If the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture exceeds the above range, the expected effect may be reduced.

[0048] In addition, the molar ratio (Mg / Si) of magnesium (Mg) atoms to silicon (Si) atoms in the silicon-carbon mixture can be 0.009 to 0.55, 0.009 to 0.30, or 0.009 to 0.10. If the molar ratio (Mg / Si) of magnesium (Mg) atoms to silicon (Si) atoms in the silicon-carbon mixture satisfies the above range, the resistance during lithium deintercalation and intercalation will be reduced, thereby further improving the discharge capacity, initial efficiency, and capacity retention rate after cycling of the lithium secondary battery.

[0049] In addition, the two or more types of composite materials may include a first composite material and a second composite material having different compositions, structures, and physical properties from each other.

[0050] In addition, according to various embodiments, the content of each component contained in the first composite material and the second composite material and the mixing range thereof can be adjusted to the optimal range required to improve the performance of the lithium secondary battery. In the manufacturing method, the etching conditions and the carbon coating conditions can be adjusted in various ways, so that the physical properties of the silicon-carbon mixture, such as specific surface area, density and porosity, can be optimized. Therefore, the performance of the lithium secondary battery can be further improved, and the reliability can be further improved.

[0051] The specific structure, composition, content, and physical properties of each of the first composite material and the second composite material included in the silicon-carbon mixture are described below.

[0052] The weight ratio of the first composite material and the second composite material may be an important factor in obtaining desired performance of the lithium secondary battery.

[0053] For example, the weight ratio of the first composite material and the second composite material can be 90: 10 to 5: 95, 90: 10 to 10: 90, 90: 10 to 20: 80, 90: 10 to 50: 50, 90: 10 to 60: 40, 90: 10 to 65: 35 or 90: 10 to 70: 30. If the weight ratio of the first composite material and the second composite material meets the above range, it is easier to achieve the desired effect, especially a lithium secondary battery with excellent initial capacity and good balanced characteristics of cycle characteristics can be provided.

[0054] In addition, since the silicon-carbon mixture according to the embodiment includes the first composite material and the second composite material uniformly mixed in the above-mentioned range, a lithium secondary battery with desired usage characteristics can be obtained by adjusting the physical properties of the final silicon-carbon mixture (such as the size and porosity of silicon particles, the magnesium content, specific surface area, thermal expansion coefficient and porosity, etc.).

[0055] In the weight ratio of the first composite material and the second composite material, if the weight ratio of the first composite material and the second composite material exceeds the above range, so that the content of the first composite material is too small or the content of the second composite material is too large, it may be difficult to achieve the desired molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture; and the effect of reducing the volume expansion of silicon particles due to charging and discharging may be reduced. In this case, the cycle characteristics or discharge capacity of the lithium secondary battery may deteriorate. In addition, the capacity retention rate of the lithium secondary battery with a silicon-carbon mixture after cycling may deteriorate.

[0056] Meanwhile, the silicon-carbon mixture includes magnesium silicate. In addition, the silicon-carbon mixture may include magnesium silicate, which is included in the second composite material described below.

[0057] In addition, the carbon included in the silicon-carbon mixture may include the first carbon and the second carbon described below.

[0058] At the same time, based on the total weight of the silicon-carbon mixture, the content of magnesium (Mg) in the silicon-carbon mixture can be 0.1 wt % to 15 wt %, preferably 0.1 wt % to 10 wt %, and more preferably 0.5 wt % to 5 wt %. If the content of magnesium (Mg) in the silicon-carbon mixture is equal to or greater than the lower limit in the above range, the initial efficiency of the lithium secondary battery can be improved. If the content of magnesium (Mg) in the silicon-carbon mixture is equal to or less than the upper limit in the above range, it may be advantageous from the perspective of the charge and discharge capacity, cycle characteristics, and processing stability of the lithium secondary battery.

[0059] Based on the total weight of the silicon-carbon mixture, the content of oxygen (O) in the silicon-carbon mixture can be 1 wt% to 25 wt%, preferably 1 wt% to 21 wt%, more preferably 1 wt% to 17 wt%, and even more preferably 3 wt% to 17 wt%.

[0060] If the content of oxygen (O) in the silicon-carbon mixture is lower than the above range, the expansion degree during charging of the lithium secondary battery increases, thereby deteriorating the cycle characteristics. In addition, if the content of oxygen (O) in the silicon-carbon mixture exceeds the above range, when the silicon-carbon mixture is used as a negative electrode active material, there may be concerns that the irreversible reaction with lithium increases, thereby deteriorating the initial charge and discharge efficiency, and the silicon-carbon mixture may easily fall off from the negative electrode collector, and deteriorate the charge and discharge cycle of the lithium secondary battery.

[0061] Based on the total weight of the silicon-carbon mixture, the silicon (Si) content in the silicon-carbon mixture can be 35 wt % to 80 wt %, preferably 40 wt % to 80 wt %, more preferably 45 wt % to 80 wt %, and even more preferably 45 wt % to 70 wt %.

[0062] If the content of silicon (Si) in the silicon-carbon mixture is lower than the above range, the amount of active material used to occlude and release lithium is small, so that the charge and discharge capacity of the lithium secondary battery may be reduced. On the other hand, if the content of silicon (Si) in the silicon-carbon mixture exceeds the above range, the charge and discharge capacity of the lithium secondary battery may increase, and the expansion and contraction of the electrode during charging and discharging may increase excessively, and the negative electrode active material powder may be further powdered, which may deteriorate the cycle characteristics of the lithium secondary battery.

[0063] The content of carbon (C) in the silicon-carbon mixture may be 9 wt % to 50 wt %, preferably 9 wt % to 40 wt %, and more preferably 10 wt % to 35 wt %, based on the total weight of the silicon-carbon mixture.

[0064] If the content of carbon (C) in the silicon-carbon mixture is lower than the above range, there is a concern that the effect of enhancing conductivity may not be obvious, and the electrode life characteristics of the lithium secondary battery may deteriorate. In addition, if the content of carbon (C) in the silicon-carbon mixture exceeds the above range, the discharge capacity of the lithium secondary battery may decrease, and the bulk density may decrease, resulting in a decrease in the discharge capacity per unit volume.

[0065] Meanwhile, the silicon-carbon mixture may further include silicon oxide (also referred to as silicon oxide compound). In this case, the capacity characteristics and life characteristics of the lithium secondary battery may be further improved, and the volume expansion may be reduced. In particular, the silicon oxide may be uniformly distributed with the silicon particles. In this case, the volume expansion may be reduced.

[0066] The silicon oxide contained in the silicon-carbon mixture may include the first silicon oxide, the second silicon oxide, and combinations thereof described below.

[0067] In addition, the silicon oxide may be a compound represented by SiO x (0.4 ≤ x ≤ 2).

[0068] That is, the silicon-carbon mixture may further include silicon oxide (SiO x , 0.4 < x ≤ 2).

[0069] Specifically, based on the total weight of the silicon-carbon mixture, the amount of silicon oxide (SiO x , 0.4 < x ≤ 2) may be 0.1 wt% to 5 wt%.

[0070] If the content of the silicon oxide exceeds the above range, the silicon oxide may react with lithium to form strong base compounds such as Li4SiO4 and Li2O. The silicon oxide is preferably amorphous. If the silicon oxide is amorphous, even when the volume of the silicon particles changes during the insertion and extraction of lithium, pulverization can be prevented or alleviated, and side reactions between the silicon particles and the electrolyte can be prevented or reduced.

[0071] Meanwhile, the silicon particles contained in the silicon-carbon mixture may include the first silicon particles and the second silicon particles described below.

[0072] In addition, the silicon-carbon mixture may further include silicon aggregates in which the silicon particles are combined with each other. The silicon aggregates are described below.

[0073] When the silicon particles (such as the first silicon particles and the second silicon particles) in the silicon-carbon mixture are subjected to X-ray diffraction analysis (converted by the results of the X-ray diffraction analysis), the average value of the grain size of the silicon particles can be 1nm to 15nm, preferably 1nm to 10nm, more preferably 2nm to 8nm, and even more preferably 3nm to 6nm. In this case, the performance of the lithium secondary battery (such as discharge capacity, initial efficiency or cycle life characteristics) may be further improved.

[0074] The average particle diameter of silicon-carbon mixture (D 50 ) can be 2 μm to 15 μm, preferably 2 μm to 10 μm, and more preferably 2 μm to 6 μm.

[0075] In addition, the minimum particle diameter Dmin of the silicon-carbon mixture can be 0.3 μm or less, and the maximum particle diameter Dmax can be 8 μm to 30 μm. If both Dmin and Dmax of the silicon-carbon mixture meet the above ranges, the specific surface area of ​​the silicon-carbon mixture is reduced, thereby further improving the initial efficiency and cycle characteristics of the lithium secondary battery.

[0076] At the same time, the density of the silicon-carbon mixture can be 1.8g / cm 3 Up to 2.5g / cm 3 , preferably 2.0 g / cm 3 Up to 2.5g / cm 3 , more preferably 2.0 g / cm 3 Up to 2.4g / cm 3 If the density of the silicon-carbon mixture meets the above range, it can be more conducive to achieving the desired effect.

[0077] The specific surface area of ​​the silicon-carbon mixture (Brunauer-Emmett-Teller method; BET) can be 2 m 2 / g to 50m 2 / g, preferably 2m 2 / g to 30m 2 / g, more preferably 2m 2 / g to 8m 2 / g. If the specific surface area of ​​the silicon-carbon mixture is less than the above range, the charging and discharging characteristics of the lithium secondary battery may deteriorate. If the specific surface area of ​​the silicon-carbon mixture exceeds the above range, the contact area between the silicon-carbon mixture and the electrolyte increases, which accelerates the decomposition reaction of the electrolyte, which may cause side reactions. If the specific surface area of ​​the silicon-carbon mixture meets the above range, lithium doping and dedoping occur actively, and the irreversible capacity is reduced, so that excellent capacity characteristics and high rate characteristics can be achieved.

[0078] The silicon carbon mixture may include pores.

[0079] Additionally, the silicon-carbon mixture may include a small amount of pores.

[0080] Additionally, the silicon-carbon mixture may not include pores.

[0081] If pores are included in the silicon-carbon mixture, the diameters of the pores may be the same as or different from each other.

[0082] The pores may include internal pores.

[0083] The internal pores include inner pores (also called closed pores) and open pores. At least a portion of the pore wall may be open to form an open structure, so that it may communicate with other pores or may not communicate with other pores.

[0084] The pores may include inner pores. The inner pores refer to independent pores which are not connected with other pores because the entire pore wall is closed to form a closed structure.

[0085] The porosity may comprise open porosity.

[0086] According to an embodiment, the porosity of the silicon-carbon mixture may be 0.1% to 30%, preferably 0.1% to 20%, and more preferably 0.1% to 10%. Porosity may be used interchangeably with voids. Porosity may refer to internal porosity.

[0087] If the porosity of the silicon-carbon mixture satisfies the above range, it can produce a buffering effect for volume expansion while maintaining sufficient mechanical strength.

[0088] If the porosity of the silicon-carbon mixture (i.e., the internal porosity of the silicon-carbon mixture) is less than the above range, it may be difficult to control the volume expansion of the negative electrode active material during charging and discharging. If the porosity of the silicon-carbon mixture exceeds the above range, the mechanical strength may be reduced due to the presence of a large number of pores in the negative electrode active material, and in the process of manufacturing a lithium secondary battery, for example, in the rolling step after mixing the negative electrode active material composition (slurry) and coating, there may be concerns about the collapse of the negative electrode active material.

[0089] If the internal porosity of the silicon-carbon mixture satisfies the above range, when the silicon-carbon mixture is applied to the negative electrode active material of a lithium secondary battery, a buffering effect of volume expansion can be obtained while maintaining sufficient mechanical strength. Therefore, the problem of volume expansion caused by the use of silicon particles can be minimized to achieve high capacity and improve life characteristics.

[0090] The internal pores include open pores on the surface of the silicon-carbon mixture and internal pores.

[0091] In the present specification, the porosity may be defined by the following Equation 1. The porosity may refer to internal porosity.

[0092] [Equation 1]

[0093] Porosity (%) = pore volume per unit mass / (specific volume + pore volume per unit mass)

[0094] The porosity measurement is not particularly limited. For example, according to an embodiment of the present invention, the porosity can be measured using BELSORP (BET apparatus) of BELJAPAN, using an adsorbed gas (such as nitrogen) or mercury penetration method (Hg porosimeter).

[0095] However, in the present invention, it may be difficult to measure an accurate value using an adsorbed gas (such as nitrogen) or mercury penetration method. This may be the case where the surface of each composite material is closed by the carbon coating of the first composite material and / or the second composite material, so that nitrogen cannot enter the internal pores. In this case, the internal porosity can be obtained by adding the value obtained by the adsorbed gas (such as nitrogen) (BET) or mercury penetration method to the internal porosity of the following equation 2.

[0096] [Equation 2]

[0097] Internal porosity (%) = {1-(measured density / calculated density)} × 100

[0098] Furthermore, in Equation 2, the measured density may be measured using helium.

[0099] In silicon-carbon mixtures, when the internal pores are closed and nitrogen or mercury cannot enter the internal pores, the porosity measured by nitrogen adsorption can be considered to be close to the open porosity.

[0100] Various Examples of Silicon Carbon Mixtures

[0101] The silicon-carbon mixture can have various structures.

[0102] Specifically, depending on the porosity, the silicon-carbon mixture may include the silicon-carbon mixture (1), the silicon-carbon mixture (2), and a combination thereof.

[0103] Specifically, the silicon-carbon mixture (1) may be a silicon-carbon mixture including a small amount of pores, and the silicon-carbon mixture (2) may be a porous mixture.

[0104] In the silicon-carbon mixture according to the embodiment, silicon-carbon mixture (1) and silicon-carbon mixture (2) each having controllable porosity can be obtained by adjusting the carbon coating method and the carbon coating amount. The carbon coating layer can be formed by chemical thermal decomposition deposition (chemical vapor deposition (CVD)).

[0105] In addition, in the following method for preparing a silicon-carbon mixture, the porosity of the silicon-carbon mixture can be controlled by adjusting the etching conditions of the first composite material (e.g., etching solution (etchant), its concentration, etching time, etc.); and / or the carbon coating conditions and carbon coating amounts of the first composite material and the second composite material (e.g., type of carbon source, coating temperature, coating time, etc.). The technical significance is that the porosity of the silicon-carbon mixture can be optimized according to the characteristics required by the lithium secondary battery by this method.

[0106] Silicon Carbon Mixture(1)

[0107] The silicon-carbon mixture (1) according to the embodiment may include a small amount of pores.

[0108] Specifically, the internal porosity of the silicon-carbon mixture (1) may be 0.1% to 10%, preferably 0.1% to 8%, and more preferably 0.1% to 5%. The method for measuring the internal porosity is as described above.

[0109] If the internal porosity of the silicon-carbon mixture (1) satisfies the above range, when the silicon-carbon mixture is applied to the negative electrode active material of a lithium secondary battery, a buffering effect of volume expansion can be obtained while maintaining sufficient mechanical strength. Therefore, the problem of volume expansion caused by the use of silicon particles can be minimized to achieve high capacity and improve life characteristics.

[0110] The internal porosity of the silicon-carbon mixture (1) can be controlled by adjusting the etching conditions of the first composite material, the carbon coating conditions, and the carbon coating amounts of each of the first composite material and the second composite material.

[0111] For example, the internal porosity of the silicon composite material obtained by etching (the first-first step or the first-second step in the preparation method described below) before the first composite material is carbon-coated may be 10% to 50%, preferably 15% to 50%, and more preferably 20% to 50%. However, the internal porosity of the first composite material obtained by forming the first carbon inside the silicon composite material and forming the first carbon layer on the surface of the silicon composite material by using a chemical thermal decomposition deposition method after etching (the first-third step in the preparation method described below) can be adjusted according to the carbon coating conditions and the carbon coating amount so that the internal porosity of the silicon-carbon mixture (1) is within the above range.

[0112] That is, in the preparation method of the first composite material, a large number of internal pores existing in the silicon-carbon composite material formed after etching can be filled with carbon by carbon coating using a chemical thermal decomposition deposition method, and the amount of carbon filled in the internal pores can be adjusted by controlling the carbon coating conditions and the amount of carbon coating, so that the internal porosity of the silicon-carbon mixture (1) satisfies the above-mentioned range.

[0113] Meanwhile, the internal porosity of the silicon-carbon mixture (1) may be 0.1% to 6%, preferably 0.1% to 5%, and more preferably 0.1% to 4%.

[0114] If the internal porosity of the silicon-carbon mixture (1) satisfies the above range, when the silicon-carbon mixture is applied to the negative electrode active material of a lithium secondary battery, a buffering effect of volume expansion can be obtained while maintaining sufficient mechanical strength. Therefore, the problem of volume expansion caused by the use of silicon particles can be minimized to achieve high capacity and improve life characteristics.

[0115] If the internal porosity and / or inner porosity of the silicon-carbon mixture (1) both satisfy the above ranges, an excellent capacity retention rate can be maintained even after thousands or more cycles over a long period of time, thereby having a significant advantage in improving reliability.

[0116] Silicon Carbon Mixture(2)

[0117] The silicon-carbon mixture ( 2 ) according to the embodiment may be porous because it includes a large number of pores.

[0118] Specifically, the internal porosity of the silicon-carbon mixture (2) may be 4% to 20%, preferably 6% to 20%, and more preferably 8% to 20%.

[0119] If the internal porosity of the silicon-carbon mixture (2) satisfies the above range, volume expansion of silicon particles that may occur during charge and discharge of a lithium secondary battery can be mitigated and suppressed by the pores.

[0120] If the internal porosity of the silicon-carbon mixture (2) exceeds the above range, the mechanical strength may be reduced due to the presence of a large number of pores in the negative electrode active material, and the negative electrode active material may collapse during the process of manufacturing a lithium secondary battery, for example, in the rolling step after mixing the negative electrode active material composition (slurry) and coating.

[0121] Meanwhile, the internal porosity of the silicon-carbon mixture (2) may be 2% to 10%, preferably greater than 4% to 10%, more preferably 6% to 10%.

[0122] If the internal porosity of the silicon-carbon mixture (2) satisfies the above range, when the silicon-carbon mixture is applied to the negative electrode active material of a lithium secondary battery, a buffering effect of volume expansion can be obtained while maintaining sufficient mechanical strength. Therefore, the problem of volume expansion caused by the use of silicon particles can be minimized to achieve high capacity and improve life characteristics.

[0123] Since the silicon-carbon mixture (2) has a porous structure, the electrolyte can easily penetrate into the silicon-carbon mixture (2), thereby improving the charging and discharging characteristics of the lithium secondary battery.

[0124] Hereinafter, the first composite material and the second composite material included in the silicon-carbon mixture will be described in detail.

[0125] <First composite material>

[0126] In the silicon-carbon mixture according to the embodiment, the first composite material includes first silicon particles and first carbon.

[0127] Specifically, the first composite material may include first silicon particles. In addition, the first composite material may further include first silicon aggregates in which the first silicon particles are combined with each other.

[0128] Specifically, the first composite material may include a first silicon aggregate having a three-dimensional (3D) structure, in which two or more first silicon particles are bonded to each other. Since the first silicon particles are filled with lithium, if the first composite material does not include the first silicon particles, the capacity of the lithium secondary battery may be reduced. In particular, if a first silicon aggregate is used (in which the first silicon particles are bonded to each other), excellent mechanical properties (such as strength) can be obtained, a negative electrode active material composition with good dispersibility can be prepared, and the negative electrode active material composition can be applied to the collector with excellent processing performance.

[0129] According to an embodiment, the first composite material may include a silicon composite material including first silicon particles and first carbon.

[0130] In addition, the first silicon aggregates can be uniformly distributed inside the first composite material (specifically, inside the silicon composite material), and the first silicon particles can include silicon particles that are not bonded to each other. The first silicon particles and / or the first silicon aggregates can be uniformly distributed inside the first composite material (specifically, inside the silicon composite material). In this case, excellent electrochemical properties such as charging and discharging can be achieved.

[0131] The first composite material may include first silicon particles, specifically, first silicon aggregates (in which the first silicon particles are mutually bonded (or connected)), a first carbon layer may be formed on the surface of the first silicon particles and / or the first silicon aggregates, and the first carbon may be formed to be uniformly dispersed and / or distributed between the first silicon particles. In addition, the first carbon layer may be formed on the surface of the silicon composite material.

[0132] For example, the first composite material may include a first carbon layer on the surface of the first silicon particles and / or the first silicon aggregates and a first carbon layer on the surface of the silicon composite material including the first silicon particles and / or the first silicon aggregates.

[0133] In this specification, the term "bonded (or interconnected)" refers to a state in which silicon particles in the first composite material are bonded (fused) to at least another silicon particle and interconnected, or a structure in which silicon particles are continuously connected (silicon aggregate).

[0134] The interior of the first composite material can be more firmly coupled together by the first carbon and the first carbon layer. Therefore, during charging and discharging of the lithium secondary battery, powdering of the silicon-carbon mixture including the first composite material due to volume change can be minimized.

[0135] The first composite material is a composite material in which first silicon aggregates (in which a plurality of first silicon particles are bonded to each other) are uniformly distributed in a composite material having a structure in the form of a single block (e.g., a polyhedron, a sphere, or the like). It may be a single composite material in which the first carbon and the first carbon layer including the first carbon surround a portion of or the entire surface of one or more first silicon particles, or surround the surface of secondary first silicon particles (first silicon aggregates) formed by the aggregation of two or more first silicon particles.

[0136] In the first composite material, the interior of the silicon composite material obtained after etching and before carbon coating may have a structure similar to a three-dimensional pomegranate (hereinafter referred to as a pomegranate structure). In the pomegranate structure, a wall can be formed inside the kernel under the state that the nanoscale first silicon particles are mutually combined. In addition, the internal pores can be formed to be surrounded by these walls. The internal pores can be very evenly distributed inside the silicon composite material. The internal pores can include internal pores and open pores.

[0137] Thereafter, a large amount of first carbon may be filled into the pores by carbon coating.

[0138] That is, since the first composite material is uniformly formed in a state where the first silicon particles are surrounded by a large amount of the first carbon and the first carbon layer including the first carbon, it has the advantages that the conductive path is sufficient to ensure high conductivity and the addition of carbon-based negative electrode active materials can be reduced when manufacturing the negative electrode. In addition, the specific surface area of ​​the first composite material is appropriately adjusted, so that the performance of the lithium secondary battery can be further improved.

[0139] Meanwhile, in the X-ray diffraction analysis (converted from the X-ray diffraction analysis result), the first silicon particles may include crystalline particles, and the grain size may be 1 nm to 15 nm, preferably 1 nm to 10 nm.

[0140] If the grain size of the first silicon particles is smaller than the above range, it is difficult to form micropores inside the first composite material, the reduction in Coulomb efficiency (representing the ratio of charge capacity to discharge capacity) cannot be suppressed, and the specific surface area is too large, so that they cannot prevent oxidation problems when handled in the atmosphere. In addition, if the grain size exceeds the above range, the micropores cannot fully suppress the volume expansion of the silicon particles that may occur during charging and discharging, and cannot suppress the reduction in Coulomb efficiency (representing the ratio of charge capacity to discharge capacity) caused by repeated charging and discharging.

[0141] Specifically, when the first composite material according to the embodiment is subjected to X-ray diffraction (Cu-Kα) analysis using copper as a cathode target and calculated by the Scherrer equation based on the full width at half maximum (FWHM) of the silicon (220) diffraction peak near 2θ=47.5°, the grain size of the first silicon particles can preferably be 1 nm to 7.5 nm, more preferably 1 nm to 6 nm.

[0142] Within the above range, the smaller the grain size of the first silicon particles, the denser the obtained composite material, thereby improving the strength of the matrix. Therefore, in this case, the performance (such as discharge capacity, initial efficiency or cycle life characteristics) of the lithium secondary battery can be further improved.

[0143] In addition, the first composite material may further include amorphous silicon or silicon having a phase similar thereto. Although the first silicon particle has high initial efficiency and battery capacity, it is accompanied by very complex crystal changes through electrochemical absorption, storage and release of lithium atoms.

[0144] At the same time, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the first composite material can be 0.005 to 0.50, preferably 0.01 to 0.40, and more preferably 0.01 to 0.30. Since the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms of the first composite material meets the above range, it can be more conducive to meeting the ideal molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture. When it is applied to lithium secondary batteries, the discharge capacity and initial efficiency can be improved, and excellent capacity retention rate is provided.

[0145] In the first composite material, the first carbon may exist on the surface of the first silicon particles. In addition, the first carbon may exist on the surface and / or inside the first silicon aggregate included in the first composite material.

[0146] In addition, the first carbon may serve as a matrix, and the first silicon particles and / or first silicon aggregates and pores may be dispersed in the first carbon matrix.

[0147] Specifically, the first composite material may have a sea-island structure, where the first silicon particles or the closed pores (v) form islands, and the first carbon forms the sea. The pores include open pores and closed pores. The closed pores may include pores that are not coated with the first carbon inside.

[0148] In the first composite material, the first carbon may be present on the surface of the silicon composite particles including the first silicon particles or inside the open pores.

[0149] The state of uniform dispersion of the first silicon particles or the first carbon was confirmed by image observation of the dark-field image or the bright-field image through a transmission electron microscope (TEM).

[0150] In addition, the first carbon is also present on the surface of the first silicon particles or the first silicon aggregates. The first carbon can be used as a matrix, and the first silicon particles and the pores can be dispersed in the first carbon matrix.

[0151] In addition, the first composite material includes silicon composites and a first carbon layer on their surfaces. The first silicon particles may be present in the silicon composites, and the first carbon may be included in at least a part of the first carbon layer and inside the silicon composites.

[0152] In addition, according to the embodiment, the thickness of the first carbon layer or the amount of carbon can be controlled so that appropriate conductivity can be obtained and the lifetime characteristics can be prevented from deteriorating, thereby obtaining a negative electrode active material with high capacity.

[0153] In addition, the first composite material may further contain a first silicon oxide (SiO x , 0.1 < x ≤ 2) (also referred to as the first silicon oxide compound).

[0154] The first silicon oxide may be formed on the surface of the first silicon particles and / or the silicon aggregates.

[0155] In addition, the first silicon oxide may be uniformly distributed with the first silicon particles.

[0156] In addition, the first silicon oxide may be formed on the surface of the first silicon particles and may be uniformly distributed with the first silicon particles or the first silicon aggregates.

[0157] The first silicon oxide may be a general term for amorphous silicon oxides (oxygen-containing silicon compounds) obtained by cooling and precipitating silicon monoxide gas formed by the oxidation of metallic silicon, the reduction of silicon dioxide, or the heating of a mixture of silicon dioxide and metallic silicon.

[0158] In the SiO of the first silicon oxide x , x may be 0.4 ≤ x ≤ 2, preferably 0.6 ≤ x ≤ 1.6, more preferably 0.6 ≤ x ≤ 1.2.

[0159] In the formula SiO xIn the case where the value of x is less than the above range, during the charging and discharging of the lithium secondary battery, swelling and shrinkage may be exacerbated and the life characteristics may deteriorate. In addition, if x exceeds the above range, the problem that may occur is that as the amount of the inactive oxide increases, the initial efficiency of the lithium secondary battery decreases.

[0160] In addition, the first carbon may be present on the surface of the first silicon oxide (SiO x , 0.1 < x ≤ 2).

[0161] Meanwhile, generally, as the proportion of oxygen in the silicon-containing negative electrode active material decreases, the proportion of silicon particles as the active material increases, thereby improving the discharge capacity and discharge efficiency. However, the problem that may occur is that the volume expansion caused by the charging and discharging of the silicon particles may form cracks in the first composite material or the silicon-carbon mixture. Therefore, the cycle characteristics of the lithium secondary battery may deteriorate. To solve this problem, silica can be included in the first composite material as an inert material or an inert phase.

[0162] Specifically, since silica is an inert material or an inert phase, it can effectively mitigate the volume expansion caused by the charging and discharging of the silicon particles. Silica is a component for forming a matrix in the first composite material, which increases the mechanical strength of the matrix of the first composite material, making it more robust, and effectively inhibits the formation of cracks even during volume expansion.

[0163] In addition, with the optimization of the silica content, the decrease in the initial capacity and initial efficiency of the lithium secondary battery can be suppressed, and the cycle characteristics can be enhanced by increasing the strength of the matrix.

[0164] Specifically, according to the embodiment, based on the total weight of the first composite material, the amount of silica that the first composite material may contain is 0.3 wt% to 6 wt%, preferably 0.5 wt% to 6 wt%, more preferably 0.5 wt% to 5 wt%, even more preferably 1 wt% to 4 wt%, and most preferably 1 wt% to 3 wt%. If the content of silica is lower than the above range, the effect of enhancing the cycle characteristics of the lithium secondary battery may be negligible. If the content of silica exceeds the above range, it may be difficult to achieve the desired molar ratio of oxygen (O) atoms to silicon (Si) atoms (O / Si) in the first composite material, and the cycle characteristics or discharge capacity of the lithium secondary battery may deteriorate.

[0165] Based on the total weight of the first composite material, the content of oxygen (O) in the first composite material can be 0.1 wt% to 16 wt%, preferably 0.1 wt% to 12 wt%, more preferably 0.1 wt% to 8 wt%, and most preferably 0.1 wt% to 6 wt%.

[0166] If the oxygen (O) content in the first composite material is lower than the above range, the expansion degree during charging of the lithium secondary battery increases, thereby deteriorating the cycle characteristics. If the oxygen (O) content in the first composite material exceeds the above range, there may be concerns that the irreversible reaction with lithium increases, thereby deteriorating the initial charge and discharge efficiency, and the first composite material may easily fall off from the negative electrode collector, and deteriorate the charge and discharge cycle of the lithium secondary battery.

[0167] Meanwhile, in the first composite material, the content of silicon (Si) can be 35% to 80% by weight, preferably 40% to 80% by weight, and more preferably 50% to 80% by weight, based on the total weight of the first composite material. If the content of silicon (Si) in the first composite material is lower than the above range, the amount of active material for occluding and releasing lithium is less, thereby possibly reducing the charge and discharge capacity of the lithium secondary battery. On the other hand, if the content of silicon (Si) in the first composite material exceeds the above range, the charge and discharge capacity of the lithium secondary battery may increase, and the expansion and contraction of the electrode during charge and discharge may increase excessively, and the negative electrode active material powder may be further powdered, which may make the cycle characteristics worse.

[0168] In addition, the first composite material includes a silicon composite material and a first carbon layer on a surface thereof. The first silicon particles may be present in the silicon composite material, and the first carbon may be contained in the first carbon layer and inside of the silicon composite material.

[0169] The content of carbon (C) in the first composite material may be 10 wt % to 50 wt % based on the total weight of the first composite material. Specifically, the content of carbon (C) may be 15 wt % to 45 wt % or 15 wt % to 40 wt % based on the total weight of the first composite material.

[0170] If the content of carbon (C) in the first composite material is lower than the above range, a sufficient effect of enhancing conductivity cannot be expected, and the electrode life of the lithium secondary battery may be deteriorated. In addition, if the content of carbon (C) in the first composite material exceeds the above range, the discharge capacity of the lithium secondary battery may be reduced, and the charge and discharge capacity per unit volume may be deteriorated.

[0171] In addition, carbon (C) may also be contained in the silicon composite material. Based on the total weight of the first composite material, the content of carbon (C) contained in the silicon composite material may be 10 wt % to 45 wt %, preferably 10 wt % to 40 wt %, and more preferably 15 wt % to 38 wt %. If the carbon contained in the silicon composite material is within the above range, sufficient conductivity can be obtained.

[0172] Furthermore, the content of carbon (C) contained in the first composite material, particularly the content of carbon (C) contained in the silicon composite material may be affected by the porosity.

[0173] For example, the first composite material may include the first composite material (1), the first composite material (2), or a mixture thereof, depending on the porosity.

[0174] The first composite material (1) may include a small amount of pores, and the first composite material (2) may include a large amount of pores.

[0175] Specifically, in the first composite material (1) including a small amount of pores, the content of carbon (C) contained in the silicon composite material can be increased to 30 wt% to 45 wt% based on the total weight of the first composite material. In addition, in the porous first composite material (2) including a large amount of pores, the content of carbon (C) contained in the silicon composite material can be reduced to 10 wt% to less than 30 wt% based on the total weight of the first composite material.

[0176] By adjusting the carbon (C) content to an optimal range in this way, the porosity of the first composite material can be controlled. Thus, a silicon-carbon mixture with controllable porosity can be obtained.

[0177] In addition, the porosity of the first composite material may be controlled to adjust the content of carbon (C) in the first composite material to an optimal range.

[0178] The thickness of the first carbon layer may be 2 nm to 100 nm, preferably 10 nm to 80 nm, more preferably 10 nm to 60 nm, even more preferably 10 nm to 40 nm.

[0179] If the thickness of the first carbon layer is equal to or greater than the above lower limit, enhancement of conductivity can be achieved. If the thickness of the first carbon layer is equal to or less than the above upper limit, reduction in capacity of the lithium secondary battery can be suppressed.

[0180] For example, the average thickness of the first carbon layer can be measured by the following steps.

[0181] First, the composite material, mixture or negative electrode active material is observed at an arbitrary magnification using a transmission electron microscope (TEM). For example, the magnification is preferably a degree that can be confirmed with the naked eye. Subsequently, the thickness of the carbon layer is measured at any 15 points. In this case, it is preferred to randomly select the measurement positions as widely as possible without focusing on a specific area. Finally, the average value of the thickness of the carbon layer at the 15 points is calculated.

[0182] The first carbon layer may include at least one selected from amorphous carbon, crystalline carbon, graphene, reduced graphene oxide, carbon nanotubes, and carbon nanofibers. Specifically, the first carbon layer may include graphene. At least one selected from amorphous carbon, crystalline carbon, graphene, reduced graphene oxide, carbon nanotubes, and carbon nanofibers may be included not only in the first carbon layer present on the surface of the silicon composite material, but also in the interior of the silicon composite material, on the surface of the first silicon particle, and in the first carbon matrix.

[0183] If the first carbon layer includes amorphous carbon, the strength of the first carbon layer is appropriately maintained, so that expansion of the composite material can be suppressed.

[0184] The amorphous carbon may include at least one selected from soft carbon (low temperature calcined carbon), hard carbon, pitch carbide, mesophase pitch carbide, and calcined coke.

[0185] For example, the raw material of the asphalt can be petroleum-based, coal-based or a mixture thereof. For example, it can be coal tar pitch, petroleum pitch, an organic synthetic pitch obtained by polycondensation of condensed polycyclic aromatic compounds, or an organic synthetic pitch obtained by polycondensation of condensed polycyclic aromatic compounds containing heteroatoms. Specifically, the raw material of the asphalt can be coal tar pitch.

[0186] If pitch is used to form the first carbon layer, the conductivity of the negative electrode active material can be improved by heat treating and carbonizing the pitch raw material through a simple heat treatment process.

[0187] In addition, when the first carbon layer includes crystalline carbon, the conductivity of the negative electrode active material can be improved. The crystalline carbon can be at least one selected from plate-shaped, spherical, fibrous natural graphite and fibrous artificial graphite.

[0188] In addition, the same type of first carbon as that of the first carbon layer may be formed inside the silicon composite material.

[0189] Meanwhile, the first carbon layer of the first composite material may include one or more carbon layers or two or more carbon layers.

[0190] For example, the first carbon layer may be a single-layer structure having one layer or a multi-layer structure having two or more layers. If the first carbon layer is composed of two or more carbon layers, even if a crack is formed on the surface of one of the carbon layers, the carbon layers can be kept electrically connected until the other carbon layer without the crack is completely detached.

[0191] Specifically, if the first carbon layer of the first composite material includes a multilayer having two or more layers, it may include a first-first carbon layer and a first-second carbon layer.

[0192] The types of the first-first carbon layer and the first-second carbon layer are as described above. Here, the types of the first-first carbon layer and the first-second carbon layer may be different from each other.

[0193] For example, the first-first carbon layer may include at least one selected from amorphous carbon, crystalline carbon, graphene, carbon nanotubes, and carbon nanofibers. The first-second carbon layer may include reduced graphene oxide (RGO). The reduced graphene oxide may be formed by partially or substantially completely reducing graphene oxide.

[0194] The average particle diameter (D 50 ) may be 2 μm to 15 μm, preferably 4 μm to 10 μm, and more preferably 4 μm to 8 μm. In addition, the average particle diameter (D 50 ) is the average particle diameter (D 50 ) (i.e. the particle size or median diameter when the cumulative volume is 50%). If the average particle diameter (D 50 ) is less than the above range, there is a concern that dispersibility may be deteriorated due to agglomeration of particles of the first composite material during the preparation of a negative electrode active material composition (slurry) using the first composite material. On the other hand, if D 50 If the above range is exceeded, the expansion of the composite material particles caused by the charging of lithium ions becomes serious, and as the charging and discharging are repeated, the bonding ability between the composite material particles and the bonding ability between the particles and the collector deteriorate, so that the life characteristics may be significantly reduced. In addition, there is a concern that the activity may deteriorate due to the reduction in specific surface area.

[0195] Meanwhile, since the surface of the silicon composite material particles or the interior of the silicon composite material and its pores may be covered by the carbon coating layer, the specific surface area of ​​the first composite material may be significantly changed.

[0196] The specific surface area (Brunauer-Emmett-Teller method; BET) of the first composite material may be 2 m 2 / g to 50m 2 / g, preferably 2m 2 / g to 40m 2 / g, more preferably 2m 2 / g to 20m 2 / g. If the specific surface area of ​​the first composite material is less than the above range, the charge and discharge characteristics of the lithium secondary battery may deteriorate. If the specific surface area of ​​the first composite material exceeds the above range, it may be difficult to prepare a negative electrode active material composition (slurry) suitable for use in a negative electrode collector of a lithium secondary battery, the contact area with the electrolyte increases, the decomposition reaction of the electrolyte may be accelerated, or a side reaction of the lithium secondary battery may be caused.

[0197] The density of the first composite material may be 1.8 g / cm 3 Up to 2.5g / cm 3 , preferably 2.0 g / cm 3 Up to 2.5g / cm 3 , more preferably 2.0 g / cm 3 Up to 2.4g / cm 3 , even more preferably 2.0 g / cm 3 Up to 2.35g / cm 3 . The density may vary depending on the coating amount of the first carbon layer. Although the amount of carbon is fixed, the greater the density within the above range, the fewer pores in the first composite material. Therefore, when the silicon-carbon mixture including the first composite material is used as a negative electrode active material, the conductivity is improved and the matrix strength is enhanced, thereby improving the initial efficiency and cycle life characteristics. In this case, the density may refer to the true density. The measurement method is as described above.

[0198] If the density of the first composite material is within the above range, the cracking of the negative electrode active material can be minimized by reducing the volume expansion of the negative electrode active material during charging and discharging. Therefore, the cycle characteristics can be prevented from being deteriorated, the permeability of the electrolyte solution can be improved, and the initial charge and discharge capacity of the lithium secondary battery can be further improved.

[0199] Meanwhile, the first composite material may include pores.

[0200] In the first composite material, by adjusting the carbon coating method and the carbon coating amount, the first composite material (1) and the first composite material (2) having different porosities can be obtained. The carbon coating layer can be formed by chemical thermal decomposition deposition (chemical vapor deposition (CVD)).

[0201] Specifically, in the following method for preparing the first composite material, the porosity of the first composite material (1) and (2) can be controlled by adjusting the etching conditions (e.g., etching solution (etchant), its concentration, etching time, etc.); and / or the carbon coating conditions and carbon coating amount (e.g., type of carbon source, coating temperature, coating time, etc.).

[0202] First Composite Material (1)

[0203] The first composite material (1) according to the embodiment may include a small amount of pores.

[0204] The definition and measurement method of pores are as described above.

[0205] Specifically, the internal porosity of the first composite material (1) may be 0.1% to 10%, preferably 0.1% to 8%, more preferably 0.1% to 5%. The method for measuring the internal porosity is as described above.

[0206] If the internal porosity of the first composite material (1) satisfies the above range, when the first composite material (1) is applied to the negative electrode active material of a lithium secondary battery, a buffering effect of volume expansion can be obtained while maintaining sufficient mechanical strength. Therefore, the problem of volume expansion caused by the use of silicon particles can be minimized to achieve high capacity and improve life characteristics.

[0207] If the internal porosity of the first composite material (1) is smaller than the above range, it may be difficult to control the volume expansion of the negative electrode active material during charge and discharge.

[0208] Meanwhile, the internal porosity of the first composite material (1) may be 0.1% to 8%, preferably 0.1% to 5%, and more preferably 0.1% to 4%.

[0209] If the internal porosity of the first composite material (1) satisfies the above range, when the first composite material (1) is applied to the negative electrode active material of a lithium secondary battery, a buffering effect of volume expansion can be obtained while maintaining sufficient mechanical strength. Therefore, the problem of volume expansion caused by the use of silicon particles can be minimized to achieve high capacity and improve life characteristics.

[0210] If the internal porosity and / or the inner porosity of the first composite material (1) both satisfy the above ranges, an excellent capacity retention rate can be maintained even after thousands or more cycles for a long period of time, thereby having a significant advantage of improving reliability.

[0211] First Composite Material (2)

[0212] The first composite material (2) according to the embodiment may be porous because it includes a large number of pores.

[0213] Specifically, the internal porosity of the first composite material (2) may be greater than 10% to 40%, preferably greater than 10% to 30%, and more preferably greater than 10% to 25%.

[0214] If the internal porosity of the first composite material (2) satisfies the above range, volume expansion of silicon particles that may occur during charge and discharge of a lithium secondary battery can be mitigated and suppressed by the pores.

[0215] If the internal porosity of the first composite material (2) exceeds the above range, the mechanical strength may be reduced due to the presence of a large number of pores in the negative electrode active material, and collapse of the negative electrode active material may occur during the process of manufacturing a lithium secondary battery, for example, in the rolling step after mixing the negative electrode active material composition (slurry) and coating.

[0216] Since the first composite material (2) has a porous structure, the electrolyte can easily penetrate into the first composite material (2), thereby improving the charging and discharging characteristics of the lithium secondary battery.

[0217] Meanwhile, the internal porosity of the first composite material (2) may be 5% to 35%, preferably greater than 5% to 25%, more preferably greater than 5% to 20%.

[0218] If the internal porosity of the first composite material (2) satisfies the above range, when the first composite material (2) is applied to the negative electrode active material of a lithium secondary battery, a buffering effect of volume expansion can be obtained while maintaining sufficient mechanical strength. Therefore, the problem of volume expansion caused by the use of silicon particles can be minimized to achieve high capacity and improve life characteristics.

[0219] <Second composite material>

[0220] In the silicon-carbon mixture according to the embodiment, the second composite material may include second silicon particles, magnesium silicate, and second carbon.

[0221] According to the embodiment, due to the use of the first composite material and the second composite material, the excellent properties of the second composite material such as capacity characteristics (initial capacity) and initial efficiency can be further improved, and the problem of the second composite material (life characteristics deterioration) is also solved. In particular, since the silicon-carbon mixture includes the second composite material, magnesium silicate can maximize the enhancement effect of initial efficiency improvement, thereby improving the performance of the lithium secondary battery.

[0222] Specifically, the second composite material may include a silicon composite oxide and a second carbon layer on its surface, second silicon particles and magnesium silicate may exist in the silicon composite oxide, and the second carbon may be contained in at least one selected from the second carbon layer, the surface of the second silicon particles, and the surface of the second magnesium silicate.

[0223] In addition, the second silicon particles and magnesium silicate can be uniformly distributed inside the silicon composite oxide. In this case, excellent electrochemical characteristics can be exhibited.

[0224] The second silicon particles may include crystalline particles, amorphous particles, or particles having a phase similar thereto, or a combination thereof.

[0225] Specifically, in X-ray diffraction analysis (converted from X-ray diffraction analysis results), the second silicon particles may include crystalline particles, and the grain size may be 3 nm to 15 nm.

[0226] For example, when the second composite material is subjected to X-ray diffraction (Cu-Kα) analysis using copper as a cathode target and is calculated by the Scherrer equation based on the full width at half maximum (FWHM) of the silicon (220) diffraction peak near 2θ=47.5°, the grain size of the second silicon particles can preferably be 4nm to 15nm, more preferably 4nm to 12nm, even more preferably 4nm to 10nm, and most preferably 4nm to 8nm.

[0227] In addition, if the grain size of the second silicon particles is smaller than the above range, the initial efficiency, discharge capacity and capacity retention rate may drop sharply. If the grain size of the second silicon particles satisfies the above range, the Coulomb efficiency (representing the ratio of the charge capacity to the discharge capacity, i.e., the charge and discharge efficiency) may be improved.

[0228] In addition, the second silicon particles may be amorphous particles, crystalline particles having a grain size of 4 nm to 15 nm, or a mixed form thereof.

[0229] Although it may be advantageous for the second silicon particles to be almost 100% amorphous particles, it is difficult to obtain completely amorphous second silicon particles in the process; therefore, the second silicon particles may exist in a mixed form of amorphous particles and crystalline particles.

[0230] Furthermore, if the second silicon particles are in the mixed form of amorphous particles and crystalline particles, the ratio of the amorphous particles may be 50% or more.

[0231] If the second silicon particles include amorphous particles, crystalline particles having a grain size within the above range, or a mixture thereof, cracks may be suppressed during the first charge and discharge of the lithium secondary battery.

[0232] If some cracks are formed in the lithium secondary battery during the first charge and discharge, the cracks may gradually expand during repeated charge and discharge cycles, which may cause problems in the performance of the lithium secondary battery.

[0233] If the second silicon particles include crystalline particles, and if the grain size of the second silicon particles is smaller than the above range, the charge and discharge capacity of the lithium secondary battery may be reduced, and the properties of the material may change during storage due to increased reactivity, which may cause problems during processing.

[0234] If the second silicon particles include crystalline particles, and if the grain size of the second silicon particles is equal to or greater than the above lower limit, the excellent charging and discharging characteristics of the lithium secondary battery can be maintained. If the grain size of the second silicon particles is equal to or less than the above upper limit, the reduction in coulombic efficiency (representing the ratio of the charging capacity to the discharging capacity of the lithium secondary battery) can be suppressed.

[0235] In addition, if the second silicon particles are further crushed to an amorphous state or a grain size of 4nm to 7nm, the density can be increased and the strength can be enhanced, thereby preventing the problem of crack formation. Therefore, the initial efficiency or cycle life characteristics of the lithium secondary battery can be further improved.

[0236] The second composite material is a composite material in which second silicon aggregates (in which a plurality of second silicon particles are bonded to each other) are uniformly distributed in a composite material having a structure in the form of a single block (e.g., a polyhedron, a sphere, or the like). It may be a single composite material in which a second carbon layer including second carbon surrounds a portion of or the entire surface of one or more second silicon particles, or surrounds the surface of secondary second silicon particles (second silicon aggregates) formed by the aggregation of two or more second silicon particles.

[0237] In addition, the content of silicon (Si) in the second composite material may be 30 wt % to 60 wt %, 30 wt % to 55 wt %, 35 wt % to 55 wt %, or 35 wt % to 50 wt %, based on the total weight of the second composite material.

[0238] If the content of silicon (Si) in the second composite material satisfies the above range, the charge and discharge capacity and cycle characteristics of the lithium secondary battery may be further improved.

[0239] If the content of silicon (Si) is lower than the above range, the charge and discharge capacity of the lithium secondary battery may decrease. If the content of silicon (Si) exceeds the above range, the charge and discharge capacity of the lithium secondary battery may increase, while the shrinkage and expansion of the electrode during charge and discharge may increase excessively, and the negative electrode active material powder may be further pulverized, which may deteriorate the cycle characteristics of the lithium secondary battery.

[0240] Meanwhile, according to the embodiment, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the second composite material may be 0.8 to 1.2, preferably 0.85 to 1.2, and more preferably 0.9 to 1.2. When the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms satisfies the above range of the second composite material, the discharge capacity and the initial efficiency can be improved while maintaining an excellent capacity retention rate.

[0241] According to the embodiment, if the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the second composite material exceeds the above range, the capacity characteristics of the secondary battery may be deteriorated.

[0242] Meanwhile, the second composite material includes magnesium silicate.

[0243] Since the second composite material includes magnesium silicate, the slurry stability is excellent when a lithium secondary battery is manufactured, and when applied to a lithium secondary battery, the capacity retention rate, charge and discharge characteristics, and cycle characteristics can be improved.

[0244] Since magnesium silicate hardly reacts with lithium ions during the charge and discharge of lithium secondary batteries, it can reduce the expansion and contraction of the electrode when lithium ions are absorbed in the electrode, thereby improving the cycle characteristics of the lithium secondary battery. In addition, magnesium silicate can enhance the strength of the matrix, which is a continuous phase surrounding silicon.

[0245] Magnesium silicate can be represented by the following formula A:

[0246] [Formula A]

[0247] Mg x SiO y

[0248] In formula A, x satisfies 0.5≤x≤2, and y satisfies 2.5≤y≤4.

[0249] The magnesium silicate may include MgSiO3, Mg2SiO4 or a mixture thereof.

[0250] Specifically, the magnesium silicate may include at least one selected from MgSiO3 crystals (enstatite) and Mg2SiO4 crystals (forsterite).

[0251] In addition, according to the embodiment, magnesium silicate may include MgSiO 3 crystals, and may further include Mg 2 SiO 4 crystals.

[0252] When magnesium silicate includes a mixture of MgSiO3 crystals and Mg2SiO4 crystals, the ratio of the MgSiO3 crystals to the Mg2SiO4 crystals may vary depending on the amount of magnesium used in the raw material step.

[0253] In addition, magnesium silicate may substantially include a large amount of MgSiO 3 crystals to improve coulombic efficiency, charge and discharge capacity, initial efficiency, and capacity retention rate.

[0254] In the present specification, the phrase "substantially comprising a large amount of" a certain component may mean including the component as a main component, or mainly comprising the component.

[0255] Specifically, according to the embodiment, magnesium silicate includes MgSiO3 crystals, and further includes Mg2SiO4 crystals. In this case, in the X-ray diffraction analysis, the ratio of the intensity (IF) of the X-ray diffraction peak of Mg2SiO4 crystals appearing in the range of 2θ=22.3° to the intensity (IE) of the X-ray diffraction peak of MgSiO3 crystals appearing in the range of 2θ=30.5° to 31.5° may be greater than 0 to 1, specifically 0.1 to 1.

[0256] If a large amount of MgSiO3 crystals are substantially used in magnesium silicate, the effect of improving the cycle during charge and discharge can be increased.

[0257] If magnesium silicate includes both MgSiO3 crystals and Mg2SiO4 crystals, initial efficiency can be improved. If more Mg2SiO4 crystals are used than MgSiO3 crystals, the degree of alloying of silicon with lithium atoms decreases, and initial discharge characteristics may deteriorate.

[0258] According to the embodiment, if the second composite material includes both MgSiO 3 crystals and Mg 2 SiO 4 crystals, the initial efficiency may be further improved.

[0259] If the second composite material includes MgSiO3 crystals, then the second composite material may be combined with Mg2SiO4 crystals (e.g., with a density of 3.2 g / cm 3 ) compared to silicon (e.g., with a density of 2.33 g / cm 3 ) volume change, MgSiO3 crystal (for example, density 2.7g / cm 3 ) has a small volume change; therefore, the cycle characteristics of the lithium secondary battery can be further improved. In addition, MgSiO3 crystals and Mg2SiO4 crystals can be used as diluents or inert materials in the negative electrode active material. In addition, if MgSiO3 crystals are formed, the powdering caused by the contraction and expansion of silicon is suppressed, so that the initial efficiency can be improved.

[0260] Furthermore, magnesium silicate hardly reacts with lithium ions; therefore, when magnesium silicate is contained in an electrode, it is possible to reduce the shrinkage and expansion of the electrode when lithium ions are absorbed and improve the cycle characteristics.

[0261] Furthermore, magnesium silicate can enhance the strength of a matrix that is a continuous phase surrounding the second silicon particles.

[0262] Since the second composite material includes magnesium silicate, when manufacturing a lithium secondary battery, a chemical reaction between a negative electrode active material and a binder can be suppressed, the stability of the slurry can be improved, and the stability and cycle characteristics of the negative electrode can be improved at the same time.

[0263] In addition, when the magnesium silicate includes both MgSiO3 crystals and Mg2SiO4 crystals, it is preferred that the MgSiO3 crystals and Mg2SiO4 crystals are uniformly distributed. Their grain size is preferably 10 nm or less.

[0264] When the MgSiO3 crystals and Mg2SiO4 crystals are uniformly distributed, the constituent elements of the second silicon particles and the MgSiO3 crystals and Mg2SiO4 crystals diffuse into each other, and the phase interface is in a bonded state, that is, each phase is in a bonded state at the atomic level; therefore, when lithium ions are occluded and released, the volume change may be small, and even when repeatedly charged and discharged, almost no cracks may form in the negative electrode active material. Therefore, even when the number of cycles is large, the capacity hardly decreases.

[0265] Meanwhile, based on the total weight of the second composite material, the content of magnesium (Mg) in the second composite material can be 2 wt% to 20 wt%, preferably 4 wt% to 15 wt%, and most preferably 4 wt% to 12 wt%.

[0266] If the content of magnesium (Mg) in the second composite material is equal to or greater than the lower limit within the above range, the initial efficiency of the lithium secondary battery can be improved. If the content of magnesium (Mg) in the second composite material is equal to or less than the upper limit within the above range, it may have advantages in terms of improving the charge and discharge capacity, cycle characteristics, and operation stability.

[0267] In addition, as the content of magnesium (Mg) increases, the content of Mg2SiO4 crystals may also increase. Therefore, the grain size of the magnesium silicate increases, resulting in an excessive increase in the initial efficiency and relatively poor cycle characteristics. Therefore, it may be important to control the content of magnesium (Mg) within the optimal range.

[0268] The magnesium silicate can be formed to be uniformly distributed with the second silicon particles.

[0269] Meanwhile, the second composite material may include a second silicon oxide (also referred to as a second silicon oxide compound).

[0270] The second silicon oxide may include the same or similar compounds as the first silicon oxide.

[0271] In addition, the second silicon oxide can be, for example, a silicon-based oxide represented by the formula SiO x (0.5 ≤ x ≤ 1.5). The second silicon oxide can specifically be SiO x (0.8 ≤ x ≤ 1.2), and more specifically SiO x (0.9 < x ≤ 1.1). In the formula SiO xIn the embodiment of the present invention, if the value of x is less than the above range, during the charge and discharge of the lithium secondary battery, expansion and contraction may be aggravated and the life characteristics may be deteriorated. In addition, if x exceeds the above range, there may be a problem that the initial efficiency of the lithium secondary battery decreases as the amount of the inactive oxide increases.

[0272] The second silicon oxide may be obtained by a method comprising mixing and heating silicon powder and silicon dioxide powder; and cooling and separating silicon oxide gas generated thereby.

[0273] The second silicon oxide may be used in an amount of 0.1 wt % to 45 wt %, preferably 0.5 wt % to 20 wt %, based on the total weight of the second composite material.

[0274] If the content of the second silicon oxide is below the above range, the volume expansion and life characteristics of the lithium secondary battery may be deteriorated. If the content of the second silicon oxide exceeds the above range, the initial irreversible reaction of the lithium secondary battery may increase.

[0275] According to the embodiment, the silicon composite oxide in the second composite material may include a second silicon oxide, and the second silicon particles, magnesium silicate, and the second silicon oxide may be uniformly mixed and present. In addition, the second silicon oxide may exist on the surface of the second silicon particles.

[0276] When the second composite material includes the second silicon particles, the second silicon oxide and magnesium silicate, the volume change when the lithium ions are absorbed and released is reduced, and cracks can be prevented from forming in the negative electrode active material during repeated charging and discharging. In this case, since the capacity relative to the number of cycles of the lithium secondary battery can be prevented from dropping sharply, the cycle characteristics of the lithium secondary battery can be improved.

[0277] In addition, since the second composite material contains second silicon particles, second silicon oxide and magnesium silicate, and the second silicon particles are interconnected and bonded, lithium ions are easily deintercalated when the lithium secondary battery is discharged; therefore, the balance between the charge and discharge amounts of lithium ions is good, and the initial efficiency (charging and discharging efficiency) can be improved.

[0278] The second silicon oxide may be used in an amount of 40 wt % to 50 wt % based on the total weight of the second composite material.

[0279] If the content of the second silicon oxide is below the above range, the volume expansion and life characteristics of the lithium secondary battery may be deteriorated. If the content of the second silicon oxide exceeds the above range, the initial irreversible reaction of the lithium secondary battery may increase.

[0280] Based on the total weight of the second composite material, the content of oxygen (O) in the second composite material can be 20% to 40% by weight, preferably 25% to 40% by weight, and more preferably 25% to 35% by weight. If the content of oxygen (O) in the second composite material is lower than the above range, the expansion degree during the charging of the lithium secondary battery will increase, thereby deteriorating the cycle characteristics. In addition, if the content of oxygen (O) in the second composite material exceeds the above range, the charging and discharging cycle of the lithium secondary battery may deteriorate.

[0281] Meanwhile, according to the embodiment, the second composite material may include a second carbon layer on the surface of the silicon composite oxide, and the second carbon (C) may be included in the second carbon layer.

[0282] Since the second composite material includes the second carbon, it can provide excellent conductivity even if the electrode expands during charge and discharge, so that the performance of the lithium secondary battery can be further improved.

[0283] In addition, according to the embodiment, the second composite material may include a silicon composite oxide and a second carbon layer on the surface thereof, the second silicon particles and magnesium silicate may be present in the silicon composite oxide, and the second carbon may be contained in at least one selected from the second carbon layer, the surface of the second silicon particles, and the surface of the second magnesium silicate. In addition, the second carbon may be present on the surface of the second silicon oxide.

[0284] Specifically, the second carbon may be included in the second carbon layer. In addition, the second carbon may be included by forming the second carbon layer on at least a portion of one or more surfaces selected from the group consisting of the second silicon particles, the second magnesium silicate, and the second silicon oxide.

[0285] More specifically, the second carbon may be contained in a second carbon layer formed on the surface of the silicon composite oxide. In addition, the second carbon may also be contained in a second carbon layer formed on at least a portion of the second silicon particle surface, the second silicon oxide particle surface, and the second magnesium silicate particle surface.

[0286] Since the second carbon is included in the second carbon layer, the mechanical properties can be enhanced, excellent conductivity can be ensured even if the electrode expands during charging and discharging, and side reactions with the electrolyte can be suppressed, thereby improving the charging and discharging capacity, initial charging and discharging efficiency and capacity retention rate of the lithium secondary battery.

[0287] Furthermore, the thickness of the second carbon layer or the amount of carbon can be controlled so that appropriate conductivity can be obtained and poor life characteristics can be prevented, thereby obtaining a negative electrode active material having a high capacity.

[0288] In addition, the content of carbon (C) in the second carbon composite material may be relatively smaller than the content of carbon (C) in the first composite material.

[0289] The carbon (C) content in the second composite material may be 3 wt % to 15 wt %, preferably 3 wt % to 10 wt %, more preferably 3 wt % to 8 wt %, and most preferably 5 wt % to 8 wt %, based on the total weight of the second composite material.

[0290] If the content of carbon (C) in the second composite material is lower than the above range, the thickness of the second carbon layer is too thin, so that the expected effect of conductivity and suppression of volume expansion may be negligible, and irreversible reactions may occur, resulting in a significant decrease in discharge capacity. In addition, if the content of carbon (C) in the second composite material exceeds the above range, the thickness of the second carbon layer is too thick, making it difficult for lithium ions to be deintercalated. In this case, the initial efficiency and discharge capacity of the lithium secondary battery may be reduced.

[0291] The thickness of the second carbon layer can be 10nm to 150nm, preferably 20nm to 100nm, and more preferably 20nm to 80nm. If the thickness of the second carbon layer meets the above range, the pulverization of the second composite material can be effectively prevented or reduced, and the side reaction between the second silicon particles and the electrolyte can be effectively prevented, thereby further improving the performance of the lithium secondary battery.

[0292] If the thickness of the second carbon layer is equal to or greater than the lower limit in the above range, conductivity enhancement can be achieved. If the thickness of the second carbon layer is equal to or less than the upper limit in the above range, reduction in capacity of the lithium secondary battery can be suppressed.

[0293] The method for measuring the average thickness of the second carbon layer is as described above.

[0294] The second carbon layer may include at least one selected from amorphous carbon, crystalline carbon, graphene, reduced graphene oxide, carbon nanotubes, and carbon nanofibers. Specifically, the second carbon layer may include at least one selected from amorphous carbon and crystalline carbon. The type of the second carbon layer is as described for the first carbon layer.

[0295] The second carbon layer may include one or more carbon layers.

[0296] When the second composite material includes a second carbon layer having one or more layers, each carbon layer can be formed thinly and uniformly along the entire outer shape of the carbon layer while maintaining the outer shape of the carbon layer. A portion or most of the second carbon layer may surround the entire surface of the silicon composite oxide. In this case, when the second carbon layer is thinly and uniformly formed on the surface of the silicon composite oxide, electrical contact between particles included in the second composite material or the negative electrode active material may be enhanced.

[0297] Specifically, if the second carbon layer of the second composite material includes a multilayer having two or more layers, it may include a second-first carbon layer and a second-second carbon layer.

[0298] The types of the second-first carbon layer and the second-second carbon layer are as described above. Here, the types of the second-first carbon layer and the second-second carbon layer may be different from each other.

[0299] The average particle diameter of the second composite material (D 50 ) can be 2 μm to 15 μm, preferably 3 μm to 12 μm, more preferably 4 μm to 10 μm, even more preferably 4 μm to 7 μm, most preferably 4 μm to 6 μm.

[0300] If the average particle diameter (D 50 ) is less than the above range, when the second composite material is used to prepare a negative electrode active slurry (negative electrode active material composition), the dispersion may be deteriorated due to the aggregation of the second composite material particles. On the other hand, if D 50 If the above range is exceeded, the expansion of the composite material particles due to lithium ion charging will become serious, and with repeated charging and discharging, the bonding ability between the composite material particles and the bonding ability between the particles and the collector will deteriorate, so that the life characteristics may be significantly reduced, and the activity may also be reduced due to the reduction in specific surface area.

[0301] In addition, according to the embodiment, the second composite material may have a composite structure, wherein the second silicon particles, the second silicon oxide and magnesium silicate are simultaneously included, and these components are uniformly dispersed. In addition, the various components or their particle sizes included in the second composite material can be adjusted within a specific range. If the sizes of the second silicon particles, the second silicon oxide and the magnesium silicate particles are each too large, the problem of not being able to fully exert the expected function of the second composite material may occur.

[0302] Meanwhile, the specific surface area (Brunauer-Emmett-Teller method; BET) of the second composite material may be 3 m 2 / g to 20m 2 / g, preferably 3m 2 / g to 15m 2 / g, more preferably 3m 2 / g to 10m 2 / g. If the specific surface area of ​​the second composite material is less than the above range, the output characteristics of the lithium secondary battery may deteriorate. If the specific surface area of ​​the second composite material exceeds the above range, it may be difficult to prepare a negative electrode active slurry suitable for use in a negative electrode collector of a lithium secondary battery, the contact area with the electrolyte increases, the decomposition reaction of the electrolyte may be accelerated, or a side reaction of the lithium secondary battery may be caused.

[0303] The density of the second composite material can be 1.8 g / cm 3 Up to 2.5g / cm3 , preferably 2.0 g / cm 3 Up to 2.5g / cm 3 , more preferably 2.0 g / cm 3 Up to 2.4g / cm 3 The density may vary depending on the coating amount of the second carbon layer. In this case, the density may refer to the true density. The measurement method is as described above.

[0304] If the density of the second composite material satisfies the above range, the permeability of the electrolyte is improved, so that the initial charge and discharge capacity and life characteristics of the lithium secondary battery can be further improved.

[0305] Meanwhile, according to the embodiment, the second composite material may include a silicate containing other metals in addition to magnesium. Other metals may be at least one selected from alkali metals, alkaline earth metals, elements of Groups 13 to 16, transition metals, rare earth elements, and combinations thereof. Specific examples thereof may include Li, Ca, Sr, Ba, Y, Ti, Zr, Hf, V, Nb, Cr, Mo, W, Fe, Pb, Ru, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, and Se.

[0306] The lithium secondary battery using the second composite material in the negative electrode can further improve its discharge capacity, initial efficiency and capacity retention rate.

[0307] According to the embodiment, by appropriately selecting and adjusting at least one of the first composite material (1) and (2) as the first composite material and the second composite material, a silicon-carbon mixture having desired physical properties can be obtained, specifically, a silicon-carbon mixture (1) and (2) having desired physical properties.

[0308] For example, the silicon-carbon mixture may include a first composite material (1) and a second composite material.

[0309] Alternatively, the silicon-carbon mixture may include a first composite material (2) and a second composite material.

[0310] Alternatively, the silicon-carbon mixture may include a first composite material (1), a first composite material (2), and a second composite material.

[0311] [Method for preparing silicon-carbon mixture]

[0312] The method for preparing a silicon-carbon mixture according to the embodiment includes: a first step of obtaining a first composite material; a second step of obtaining a second composite material; and a third step of mixing the first composite material and the second composite material, wherein the first composite material comprises first silicon particles and first carbon, and the second composite material comprises second silicon particles, magnesium silicate, and second carbon.

[0313] According to the method for preparing the silicon-carbon mixture, the etching conditions and the carbon coating conditions can be adjusted in various ways, so that the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture and its physical properties (such as specific surface area, density and porosity) can be adjusted and optimized in various ways. Therefore, the performance of the lithium secondary battery can be further improved, and the reliability can be further improved.

[0314] Furthermore, the preparation method has an advantage in that large-scale production can be performed through a continuous process with a minimum number of steps.

[0315] First step to obtain the first composite material

[0316] First, the method for preparing a silicon-carbon mixture includes: a first step of obtaining a first composite material including first silicon particles and first carbon.

[0317] The first step of obtaining the first composite material may include: a first-first step of etching a first silicon-based raw material powder using an etching solution, wherein the etching solution contains a compound containing fluorine (F) atoms; a first-second step of filtering and drying the product obtained by etching to obtain a silicon composite material; and a first-third step of forming a first carbon inside the silicon composite material and a first carbon layer on the surface of the silicon composite material using a chemical thermal decomposition deposition method to obtain the first composite material.

[0318] The first-first step may include etching the first silicon-based raw material powder using an etching solution including a compound containing fluorine (F) atoms.

[0319] The first silicon-based raw material powder may include a powder including silicon capable of reacting with lithium, for example, a powder including at least one of silicon, silicon oxide, and silicon dioxide.

[0320] Specifically, the first silicon-based raw material powder may include, for example, at least two of silicon, silicon oxide, and silicon dioxide. Specifically, the first silicon-based raw material powder may include a x Low-order silicon oxide powder represented by (0.9≤x<1.2).

[0321] The first silicon-based raw material powder may be an amorphous or crystalline SiO prepared by a gas phase method. x(Silicon crystal size: about 2 nm to 3 nm) The average particle diameter (as a median diameter) of the first silicon-based raw material powder may be about 0.5 μm to 30 μm, preferably 0.5 μm to 25 μm, and more preferably 0.5 μm to 10 μm.

[0322] If the average particle diameter of the first silicon-based raw material powder is smaller than the above range, the volume density may be too small, so that the charge and discharge capacity per unit volume may be deteriorated. If the average particle diameter of the first silicon-based raw material powder exceeds the above range, it may be difficult to manufacture an electrode, or it may peel off from the collector. The average particle diameter may be D in particle size distribution measurement by laser diffraction. 50 (i.e. the particle diameter when the cumulative weight is 50%).

[0323] In addition, the method may further include: forming a carbon layer on the surface of the first silicon-based raw material powder using a chemical thermal decomposition deposition method. Therefore, the first silicon-based raw material powder on which the carbon layer has been formed may be used as the silicon-based raw material powder.

[0324] Specifically, once a carbon layer is formed on the surface of the first silicon-based raw material powder containing silicon particles, the first-first step etching step may be performed. In this case, there may be advantages that uniform etching may be performed and high yield may be obtained.

[0325] The step of forming the carbon layer may be performed by a process similar to or the same as the process of forming the first carbon layer in the first to third steps of the method for preparing the first composite material described below.

[0326] The etching step may include dry etching and wet etching.

[0327] If dry etching is used, selective etching can be performed.

[0328] Silicon oxide in the first silicon-based raw material powder is dissolved and eluted by the etching step, thereby forming pores.

[0329] In addition, the pores can also be considered to be formed by, for example, the following reaction formulas 2 and 3.

[0330] [Reaction 2]

[0331] SiO2+4HF(gas)→SiF4+2H2O

[0332] [Reaction 3]

[0333] SiO2+6HF(aqueous solution)→H2SiF6+2H2O

[0334] Pores (voids) may be formed at locations where silicon dioxide is dissolved and removed in the form of SiF4 and H2SiF6 by a reaction mechanism as in the above-described reaction formula.

[0335] Furthermore, depending on the degree of etching, silicon oxide (eg, silicon dioxide) included in the first composite material may be removed, and pores may be formed therein.

[0336] The degree of pore formation may vary with the degree of etching.

[0337] In addition, after etching, the ratio O / Si and the specific surface area of ​​the silicon composite material may change significantly, respectively. In addition, the specific surface area and density of the silicon composite material forming pores may change significantly before and after carbon coating.

[0338] By etching, a silicon composite material powder having a plurality of pores formed on the surface of the silicon composite material particles or on the surface and inside of the silicon composite material particles can be obtained.

[0339] Here, etching refers to a process of treating the first silicon-based raw material powder with an etching solution containing a compound containing fluorine (F) atoms.

[0340] As the etching solution containing the fluorine (F) atom-containing compound, a commonly used fluorine atom-containing etching solution may be used without limitation within a range not impairing the effect.

[0341] Specifically, the compound containing fluorine (F) atoms may include at least one selected from HF, NH 4 F, and HF 2. When the compound containing fluorine (F) atoms is used, the etching step may be performed faster.

[0342] The etching solution may further include one or more acids selected from the group consisting of organic acid, sulfuric acid, hydrochloric acid, phosphoric acid, nitric acid, and chromic acid.

[0343] As etching conditions, the stirring temperature (processing temperature) may be, for example, 10°C to 90°C, preferably 10°C to 80°C, and more preferably 20°C to 70°C.

[0344] The silicon composite material obtained after etching may include first silicon particles.

[0345] The silicon composite material having a plurality of pores formed on the surface, inside, or on the surface and inside of the silicon composite material particles can be obtained by etching. Here, the silicon composite material can have a three-dimensional (3D) structure in which two or more first silicon particles are bonded to each other.

[0346] Furthermore, it is also characterized in that the average particle diameter of the silicon composite material hardly changes due to etching.

[0347] That is, the average particle diameter of the first silicon-based raw material powder before etching is approximately the same as the average particle diameter of the silicon composite material obtained by etching. The difference (variation) in the average particle diameters of the first silicon-based raw material powder and the silicon composite material may be within about 5%.

[0348] In addition, the amount of oxygen present on the surface of the silicon composite material can be reduced by etching. That is, the oxygen content on the surface of the silicon composite material can be significantly reduced by etching and the surface resistance can be reduced. In this case, the electrochemical characteristics of the lithium secondary battery, particularly the life characteristics, can be further improved.

[0349] In addition, since a large amount of silicon oxide (silicon dioxide) is removed by selective etching, the surface of the first silicon particle can contain a very high fraction of silicon (Si) compared to oxygen (O). That is, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms present in the silicon composite material can be significantly reduced. In this case, a lithium secondary battery with excellent capacity retention and improved discharge capacity and initial efficiency can be obtained.

[0350] Furthermore, pores or voids may be formed at locations where silicon oxide (silicon dioxide) is removed. As a result, the specific surface area of ​​the silicon composite material may be increased compared to the specific surface area of ​​the first silicon-based raw material powder before etching.

[0351] According to the embodiment, physical properties such as element content and specific surface area may vary before and after the etching step. That is, the physical properties (such as element content and specific surface area) of the first silicon-based raw material powder before the etching step may be different from the physical properties of the silicon composite material after the etching step.

[0352] Here, unless otherwise specified, both the silicon composite material after the etching step and before the carbon coating and the second silicon composite material have a porous structure.

[0353] After the etching step, the internal porosity of the silicon composite material may be 10% to 50%, preferably 15% to 50%, and more preferably 20% to 50%.

[0354] If the internal pores of the silicon composite material meet the above range, it may be more conducive to achieving the desired effect.

[0355] In the method for preparing the first silicon composite material, the first-second step may include filtering and drying the product obtained by etching to obtain the silicon composite material. The filtering and drying steps may be performed by a common method.

[0356] In the process for preparing the first composite material, the first to third steps may include forming a first carbon inside the silicon composite material and forming a first carbon layer on a surface of the silicon composite material by using a chemical thermal decomposition deposition method to prepare the first composite material.

[0357] The first carbon layer may include at least one selected from amorphous carbon, crystalline carbon, graphene, reduced graphene oxide, carbon nanotubes, and carbon nanofibers.

[0358] The step of forming the first carbon inside the silicon composite material and forming the first carbon layer on the surface of the silicon composite material can be performed by injecting at least one carbon source gas selected from the compounds represented by the following formulas 1 to 3 and reacting the silicon composite material obtained in the first-second steps in a gaseous state at 400°C to 1200°C.

[0359] [Formula 1]

[0360] C N H (2N+2-A) [OH] A

[0361] In Formula 1, N is an integer from 1 to 20, and A is 0 or 1,

[0362] [Formula 2]

[0363] C N H (2N-B)

[0364] In Formula 2, N is an integer from 2 to 6, and B is an integer from 0 to 2,

[0365] [Formula 3]

[0366] C x H y O z

[0367] In Formula 3, x is an integer from 1 to 20, y is an integer from 0 to 25, and z is an integer from 0 to 5.

[0368] The compound represented by Formula 1 may be at least one selected from methane, ethane, propane, butane, methanol, ethanol, propanol, propylene glycol and butanediol. The compound represented by Formula 2 may be at least one selected from ethylene, acetylene, propylene, butylene, butadiene and cyclopentene. The compound represented by Formula 3 may be at least one selected from benzene, toluene, xylene, ethylbenzene, naphthalene, anthracene and butylated hydroxytoluene (BHT).

[0369] The carbon source gas may further include at least one inert gas selected from the group consisting of hydrogen, nitrogen, helium, and argon.

[0370] The reaction may be performed, for example, at 400°C to 1200°C, specifically 500°C to 1100°C, more specifically 600°C to 1000°C.

[0371] The reaction time (or heat treatment time) can be appropriately adjusted according to the heat treatment temperature, the pressure during the heat treatment, the composition of the gas mixture and the desired amount of carbon coating. For example, the reaction time can be 10 minutes to 100 hours, specifically 30 minutes to 90 hours, more specifically 50 minutes to 40 hours, but is not limited thereto.

[0372] According to the method for preparing the first composite material according to the embodiment, a thin and uniform first carbon layer can be formed on the surface of the silicon composite material by the gas phase reaction of the carbon source gas even at a relatively low temperature. In addition, substantially no separation reaction occurs in the first carbon layer thus formed.

[0373] Furthermore, since the first carbon layer is uniformly formed on the entire surface of the silicon composite material by a gas phase reaction using a chemical pyrolysis deposition method, a carbon film (carbon layer) having high crystallinity can be formed.

[0374] In addition, carbon can be coated (embedded) in multiple pores formed by etching in the first-first step and / or the first-second step through a gas phase reaction using a chemical thermal decomposition deposition method, so that the porosity of the first composite material and the silicon-carbon mixture can be controlled and the desired effect can be achieved.

[0375] Therefore, when the silicon-carbon mixture including the first composite material is used as a negative electrode active material, the conductivity of the negative electrode active material can be improved without changing the structure.

[0376] According to the embodiment, when the reaction gas containing the carbon source gas and the inert gas is supplied to the silicon composite material, the reaction gas can penetrate into the pores of the silicon composite material, thereby fully forming (coating or embedding) the first carbon inside the silicon composite material and forming a first carbon layer on the surface of the silicon composite material. Therefore, the conductivity of the negative electrode active material can be improved.

[0377] The specific surface area of ​​the first composite material may be reduced relative to the amount of carbon coating.

[0378] In addition, the porosity of the first composite material and the porosity of the silicon-carbon mixture can be controlled as needed by adjusting the etching conditions and / or the carbon coating conditions. That is, as the carbon penetrates and fills the pores of the silicon composite material, a carbon layer is formed on the surface of the silicon composite material, and a first composite material with controllable porosity can be obtained, specifically the first composite material (1) and the first composite material (2). Through this method, the porosity of the silicon-carbon mixture can be optimized according to the characteristics required for the lithium secondary battery.

[0379] The structure of the graphene-containing material may be a layer, a nanosheet type, or a structure in which a plurality of sheets are mixed.

[0380] If the first carbon layer containing the graphene-containing material is uniformly formed on the entire surface of the silicon composite material, volume expansion can be suppressed because the graphene-containing material having improved conductivity and flexibility to volume expansion is directly grown on the surface of the first silicon particles. In addition, the coating of the first carbon layer can reduce the chance of direct contact between silicon and the electrolyte, thereby reducing the formation of a solid electrolyte interface (SEI) layer.

[0381] Meanwhile, after a large number of pores formed after etching are coated with carbon, the first carbon may be embedded into the surface and internal pores of the first composite material.

[0382] The porosity of the first composite material after carbon coating is as described above.

[0383] In addition, according to the embodiment, after the first-third step (wherein the first carbon is formed inside the silicon composite material in the first-third step, and the first carbon layer is formed on the surface of the silicon composite material), one or more first composite materials may be combined with each other to form aggregates. It may further include pulverizing and classifying the first composite material so that the average particle diameter of the first composite material is 2 μm to 15 μm. Classification may be performed to adjust the particle size distribution of the first composite material, for which dry classification, wet classification or classification using a screen may be used. In dry classification, air flow is used to sequentially or simultaneously perform the steps of dispersion, separation, collection (separation of solids and gases) and discharge, wherein pretreatment (adjustment of moisture, dispersibility, humidity, etc.) may be performed before classification to avoid interference between particles, particle shape, air flow disturbance, velocity distribution, and electrostatic effects, etc., causing the classification efficiency to decrease, thereby adjusting the moisture or oxygen concentration in the air flow used. In addition, the desired particle size distribution may be obtained by simultaneously pulverizing and classifying the first composite material. After pulverization, the coarse powder portion and the particle portion are effectively separated by a classifier or a screen.

[0384] Second step to obtain the second composite material

[0385] The method for preparing a silicon-carbon mixture according to the embodiment includes a second step of obtaining a second composite material including second silicon particles, magnesium silicate, and second carbon.

[0386] The method for obtaining the second composite material includes: a second-first step of obtaining a silicon composite oxide by using a second silicon-based raw material and a magnesium-based raw material; a second-second step of pulverizing and / or classifying the silicon composite oxide to obtain a silicon composite oxide powder; and a second-third step of forming a second carbon layer on the surface of the silicon composite oxide powder using a chemical thermal decomposition deposition method to obtain the second composite material.

[0387] The method for preparing the second composite material has the advantage that it can be produced on a large scale by a continuous process with a minimum of steps.

[0388] Specifically, in the method for preparing the second composite material, the second-first step may include obtaining a silicon composite oxide by using a silicon-based raw material and a magnesium-based raw material. The second-first step may be performed by, for example, using the method described in Korean Laid-Open Patent Publication No. 2018-0106485.

[0389] Furthermore, the second silicon-based raw material may be the same as or similar to the first silicon-based raw material.

[0390] The silicon composite oxide may contain magnesium silicate.

[0391] Specifically, the second silicon-based raw material and the magnesium-based raw material may be heated at different temperatures to evaporate, and then may be deposited and cooled to obtain the silicon composite oxide.

[0392] The second silicon-based raw material powder may include at least one selected from silicon, silicon oxide, and silicon dioxide.

[0393] The magnesium-based raw material may include metallic magnesium.

[0394] Meanwhile, the average particle diameter of the second silicon-based raw material is not limited. For example, the average particle diameter of the silicon powder may be 5 μm to 50 μm, 10 μm to 40 μm, or 15 μm to 30 μm, and the average particle diameter of the silicon dioxide powder may be 5 nm to 50 nm, 10 nm to 40 nm, or 15 nm to 30 nm.

[0395] If the second silicon-based raw material having an average particle diameter within the above range is used, deposition and evaporation of silicon dioxide become uniform, so that fine second silicon particles can be obtained.

[0396] The second silicon-based raw material and the magnesium-based raw material may be respectively put into crucibles in a vacuum reactor, heated at different temperatures to evaporate, and then may be deposited and cooled to obtain a silicon composite oxide.

[0397] The heating and evaporation of the second silicon-based raw material may be performed at 900° C. to 1800° C., preferably 1000° C. to 1600° C., more preferably 1200° C. to 1600° C., at a pressure of 0.0001 torr to 2 torr. If the temperature is lower than the above range, the reaction may be difficult to proceed, thereby reducing productivity. If the temperature exceeds the above range, reactivity may be reduced.

[0398] The heating and evaporation of the magnesium-based raw material may be performed at 500° C. to 1100° C., 600° C. to 1000° C., or 650° C. to 900° C. at a pressure of 0.0001 Torr to 2 Torr.

[0399] If the heating and evaporation of the second silicon-based raw material and the magnesium-based raw material satisfy the above ranges, fine second silicon particles and fine magnesium silicate particles can be produced, thereby obtaining silicon oxide (silicon oxide compound) having a desired SiOx (0.4≤x≤2) composition.

[0400] Meanwhile, the deposition may be performed at 300°C to 800°C, preferably 400°C to 700°C.

[0401] Cooling can be performed by rapidly cooling to room temperature by water cooling. In addition, it can be performed at room temperature while injecting an inert gas. The inert gas can be at least one selected from carbon dioxide gas, argon (Ar), helium (He), nitrogen (N2) and hydrogen (H2).

[0402] The second silicon-based raw material and the magnesium-based raw material are heated and evaporated, and then deposited on a substrate in a reactor to synthesize a silicon composite oxide by a uniform gas phase reaction of the particles; therefore, the rapid growth of the second silicon due to an exothermic reaction caused by excessive local mixing of magnesium, as in a solid-state reaction, can be avoided.

[0403] At the same time, the silicon composite oxide may be further subjected to heat treatment.

[0404] The heat treatment may be performed at a temperature of 700° C. to 950° C. Specifically, the heat treatment may be performed at a temperature of 800° C. to 950° C. (preferably 900° C. to 930° C.) for 1 to 10 hours or 1 to 5 hours.

[0405] The second-second step according to the embodiment may further include pulverizing and / or classifying the silicon composite oxide obtained in the second-first step so that its average particle diameter is 3 μm to 15 μm.

[0406] More specifically, the silicon composite oxide obtained in the second-first step may be pulverized, and the pulverization may be performed so that the average particle diameter (D 50 ) is 3 μm to 10 μm, specifically 3 μm to 8 μm.

[0407] For pulverization, pulverization devices well known in the art can be used. For example, at least one selected from a jet mill, a ball mill, a stirred media mill, a roller mill, a hammer mill, a pin mill, a disc mill, a colloid mill and an atomizer mill can be used for pulverization.

[0408] Specifically, the pulverization can be carried out using a ball mill or a stirred medium mill, which moves a pulverizing medium (such as a ball and a bead), and the object to be pulverized is pulverized by the impact force, friction force or compression force provided by kinetic energy, or a roller mill is used for pulverization, and the roller mill is pulverized by the compression force of the roller. In addition, a jet mill can also be used to make the object to be pulverized collide with the internal material or collide with each other at high speed, and the impact force generated by the collision is pulverized. In addition, a hammer mill, a pin mill or a disc mill can also be used. In addition, a colloid mill or an atomizer mill using shear force can also be used as a high-pressure wet reverse impact type disperser.

[0409] Furthermore, classification may be performed using at least one selected from dry classification, wet classification, or screen classification.

[0410] According to an embodiment, dry classification equipped with a cyclone and a jet mill may be used.

[0411] In a jet mill, the processes of dispersion, separation (separation of fine and coarse particles), collection (separation of solids and gases) and discharge can be carried out in sequence using air flow. In this case, interference between particles, particle shape, air flow disturbance, velocity distribution and the influence of static electricity will not impair the classification efficiency.

[0412] That is, before classification, the airflow may be pre-treated (adjusting moisture, dispersion, humidity, etc.) to adjust the concentration of moisture and oxygen.

[0413] Furthermore, a desired particle size distribution can be achieved by simultaneously performing pulverization and classification.

[0414] In the process for preparing the second composite material, the second-third step may include forming a second carbon layer on the surface of the silicon composite oxide powder using a chemical thermal decomposition deposition method to obtain the second composite material.

[0415] The second carbon layer may be formed on the surface of the silicon composite oxide powder as well as on the surface of at least one particle selected from the group consisting of second silicon particles, magnesium silicate (particles), and second silicon oxide (particles) constituting the silicon composite oxide powder.

[0416] The second carbon layer may include at least one selected from amorphous carbon, crystalline carbon, graphene, reduced graphene oxide, carbon nanotubes, and carbon nanofibers.

[0417] The step of forming the second carbon layer can be performed in the same manner as the first to third steps.

[0418] In addition, according to the embodiment, it may further include, after the second-third step (after forming the second carbon layer in the second-third step), pulverizing and classifying the second composite material so that the second composite material has a desired average particle diameter. The pulverizing and classifying steps are as described above.

[0419] Step 3

[0420] The method for preparing a silicon-carbon mixture includes a third step of mixing a first composite material and a second composite material.

[0421] The mixing weight ratio of the first composite material and the second composite material can be 90:10 to 5:95, 90:10 to 10:90, 90:10 to 20:80, 90:10 to 60:40, 90:10 to 65:35 or 90:10 to 70:30. If the mixing weight ratio of the first composite material and the second composite material meets the above range, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture can be optimized. Therefore, a silicon-carbon mixture with desired properties can be obtained.

[0422] If the mixing weight ratio of the first composite material and the second composite material exceeds the above range, it is difficult to achieve the expected effects, and in particular, the cycle characteristics of the lithium secondary battery may be deteriorated.

[0423] The mixing may be performed by at least one method selected from dry mixing and wet mixing.

[0424] According to an embodiment, mixing can be performed using, for example, a co-rotating mixer to prepare a powder containing mixed phase particles. The rotation speed during mixing can be 1000 rpm to 3000 rpm, for example, about 2000 rpm, and the mixing time can be 2 minutes to 20 minutes, preferably 3 minutes to 10 minutes, more preferably 5 minutes to 8 minutes, for example, about 6 minutes. If the mixing speed and mixing time are within the above range, the first composite material and the second composite material can be effectively and uniformly mixed.

[0425] Meanwhile, according to the embodiment, the silicon-carbon mixture can be prepared by the following preparation method, which includes: mixing the silicon composite material obtained in the first-second step with the silicon composite oxide powder obtained in the second-second step to prepare a silicon composite material mixture; and forming a carbon layer on the silicon composite material mixture.

[0426] In the silicon composite material mixture, the mixing weight ratio of the silicon composite material obtained in the first-second step to the silicon composite oxide powder obtained in the second-second step can be 90:10 to 5:95, 90:10 to 10:90, 90:10 to 20:80, 90:10 to 60:40, 90:10 to 65:35, or 90:10 to 70:30. If the mixing weight ratio of the silicon composite material mixture meets the above range, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture can be optimized. Therefore, a silicon-carbon mixture with desired properties can be obtained.

[0427] In addition, the step of forming a carbon layer on the silicon composite material mixture can be performed in the same or similar manner as the first to third steps. The method can further include: a step of pulverizing the powder obtained after forming the carbon layer (pulverizing step). The pulverizing step is as described above.

[0428] Negative electrode active material

[0429] The negative electrode active material according to the embodiment may include a silicon-carbon mixture.

[0430] In addition, the negative electrode active material may further include a carbon-based negative electrode material (specifically, a graphite-based negative electrode material).

[0431] When the negative electrode active material is used as a mixture of a silicon-carbon mixture and a carbon-based negative electrode material (e.g., a graphite-based negative electrode material), the resistance of the negative electrode active material can be reduced, and the expansion stress involved in charging can be alleviated. The carbon-based negative electrode material may include, for example, at least one selected from natural graphite, synthetic graphite, soft carbon, hard carbon, mesophase carbon, carbon fiber, carbon nanotube, pyrolytic carbon, coke, glass carbon fiber, sintered organic polymer compound and carbon black.

[0432] The carbon-based negative electrode material may be contained in an amount of 5 to 70 wt %, preferably 10 to 60 wt %, and more preferably 10 to 50 wt %, based on the total weight of the negative electrode active material.

[0433] In addition, if silicon particles having a crystal size of 20 nm or less (e.g., 15 nm or less) are mixed with a graphite-based material that generally has low volume expansion, the silicon particles themselves do not cause large volume expansion; therefore, a lithium secondary battery with excellent cycle characteristics can be obtained.

[0434] Lithium secondary battery

[0435] According to an embodiment, a negative electrode including a negative electrode active material and a lithium secondary battery including the negative electrode are provided.

[0436] The lithium secondary battery may include a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and a non-aqueous liquid electrolyte in which a lithium salt is dissolved. The negative electrode active material may include a negative electrode active material including a silicon-carbon mixture.

[0437] The negative electrode may be composed only of the negative electrode mixture, or may be composed of a negative electrode current collector and a negative electrode mixture layer (negative electrode active material layer) loaded thereon. Similarly, the positive electrode may be composed only of the positive electrode mixture, or may be composed of a positive electrode current collector and a positive electrode mixture layer (positive electrode active material layer) loaded thereon. In addition, the negative electrode mixture and the positive electrode mixture may further contain a conductive agent and a binder (binding agent), respectively.

[0438] As the material constituting the negative electrode current collector and the material constituting the positive electrode current collector, materials known in the art may be used. As the binder and the conductive material added to the negative electrode and the positive electrode, materials known in the art may be used.

[0439] If the negative electrode is composed of a current collector and an active material layer supported thereon, the negative electrode can be prepared by coating a negative electrode active material composition including a silicon-carbon mixture on the surface of the current collector and drying it.

[0440] In addition, the lithium secondary battery includes a non-aqueous liquid electrolyte, wherein the non-aqueous liquid electrolyte may include a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. A solvent commonly used in the art can be used as a non-aqueous solvent. Specifically, an aprotic organic solvent can be used. Examples of aprotic organic solvents include cyclic carbonates (e.g., ethylene carbonate, propylene carbonate, and butylene carbonate), cyclic carboxylates (e.g., furanone), chain carbonates (e.g., diethyl carbonate, ethyl methyl carbonate, and dimethyl carbonate), chain ethers (e.g., 1,2-methoxyethane, 1,2-ethoxyethane, and ethoxymethoxyethane) and cyclic ethers (e.g., tetrahydrofuran and 2-methyltetrahydrofuran). They can be used alone or in combination of two or more.

[0441] The lithium secondary battery may include a non-aqueous lithium secondary battery.

[0442] The negative electrode active material and the lithium secondary battery using the silicon-carbon mixture according to the embodiment can improve the charge and discharge capacity, as well as the initial charge and discharge efficiency and the capacity retention rate.

[0443] Mode for the Invention

[0444] Hereinafter, the present invention will be described in detail with reference to Examples. The following Examples merely illustrate the present invention, and the scope of the present invention is not limited thereto.

[0445] <Preparation of First Composite Material>

[0446] Preparation Example 3-1

[0447] (1) Step 1-1: 50 g of silicon oxide (SiO x , x = 0.9) powder was dispersed in water, the powder being silicon oxide (oxygen-containing silicon compound) obtained by vapor deposition using silicon powder and silicon dioxide powder (Preparation Example 1-1), and its physical properties are shown in the following Table 1. While stirring at a speed of 300 rpm, 50 ml of a 40 wt % HF aqueous solution was added as an etching solution, and the silicon-based raw material (first silicon-based raw material) powder was etched for 1 hour.

[0448] (2) Step 1-2: The product obtained by the above etching was filtered and dried at 150° C. for 2 hours to prepare a dried composite material. Then, in order to control the particle size of the composite material, it was crushed using a mortar to an average particle diameter of 4.5 μm, thereby preparing a porous silicon composite material (Preparation Example 2-1) having the contents of each component and physical properties as shown in Table 2 below.

[0449] (3) Step 1-3: 10 g of the porous silicon composite material was placed in a tubular electric furnace, and argon (Ar) and methane gas were flowed at a rate of 1 liter / minute, respectively. The mixture was kept at 900° C. for 1 hour, and then cooled to room temperature, thereby forming a first carbon inside the silicon composite material and a first carbon layer on the surface of the silicon composite material, and a first silicon-carbon composite material having the contents of each component and physical properties as shown in Table 3 below was obtained.

[0450] (4) Step 1-4: In order to control the particle size of the first silicon-carbon composite material, it is crushed and classified by a mechanical method so that its average particle diameter is 5.0 μm, thereby obtaining a first composite material having the content of each component and physical properties as shown in Table 3 below.

[0451] Preparation Examples 3-2 to 3-7

[0452] The first composite materials (Preparation Examples 3-2 to 3-7) having the contents of each component and the physical properties of the composite materials shown in Table 3 below were prepared in the same manner as Preparation Example 3-1, except that: porous silicon composite materials (Preparation Examples 2-2 to 2-5) having the contents of each component and the physical properties shown in Table 2 below were used to adjust the contents of each component and the physical properties of the composite materials.

[0453] Preparation Examples 3-8 to 3-10

[0454] The first composite material (Preparation Examples 3-8 to 3-10) having the content of each component and the physical properties of the composite material shown in Table 3 below were prepared in the same manner as Preparation Example 3-1, except that: porous silicon composite materials (Preparation Examples 2-2 to 2-5) having the content of each component and the physical properties shown in Table 2 below were used to adjust the content of each component and the physical properties of the composite material, and 10 g of the porous silicon composite material was placed in a tubular electric furnace, argon (Ar) and ethylene gas were flowed through at a rate of 0.5 liters / minute, respectively, maintained at 750°C for 2 hours, and then cooled to room temperature, thereby forming a first carbon inside the silicon composite material and a first carbon layer on the surface of the silicon composite material.

[0455] <Preparation of Second Composite Material>

[0456] Preparation Example 4-1

[0457] (1) Step 2-1: 8 kg of silicon powder having an average particle size of 20 μm and 16 kg of silicon dioxide powder having an average particle size of 20 nm were added to 50 kg of water, stirred for 12 hours to uniformly mix, and then dried at 200° C. for 24 hours to obtain a raw material powder mixture.

[0458] The raw material powder mixture and 2 kg of metal magnesium were placed in crucible-A and crucible-B in a vacuum reactor, respectively. After the pressure was reduced to 0.1 Torr, the temperature of crucible-A was raised to 1500°C, the temperature of crucible-B was raised to 900°C, and then reacted for 5 hours.

[0459] The silicon composite oxide bulk deposited on the substrate inside the reactor by a high temperature gas phase reaction is rapidly cooled to room temperature by the water-cooled substrate.

[0460] (2) Step 2-2: The silicon composite oxide bulk was pulverized by a mechanical method to control the particle size, thereby obtaining a silicon composite oxide powder having an average particle diameter of 6 μm.

[0461] (3) Step 2-3: Place 50 g of silicon composite oxide powder into a tubular electric furnace, flow argon (Ar) and methane gas at a rate of 1 liter / minute respectively, and maintain at 900°C for 1 hour to obtain a second composite material (Preparation Example 4-1) having the content of each component and physical properties of the composite material as shown in Table 4 below.

[0462] Preparation Example 4-2

[0463] A second composite material (Preparation Example 4-2) was prepared in the same manner as Preparation Example 4-1, except that the contents of the components and the physical properties of the composite material were adjusted as shown in Table 4 below.

[0464] Example 1

[0465] Preparation of silicon-carbon mixture

[0466] The first composite material of Preparation Example 3-1 and the second composite material of Preparation Example 4-1 were mixed at a weight ratio of 90:10. Here, a synchronous rotating mixer (THINKY MIXER) was used for mixing to prepare a powder containing mixed phase particles composed of the first composite material and the second composite material. The mixing was carried out at a rotation speed of 2000 rpm and the mixing time was about 6 minutes. The physical properties of the silicon-carbon mixture thus obtained are shown in Tables 5 and 7 below.

[0467] Manufacturing of lithium secondary batteries

[0468] A negative electrode and a battery (button cell) including a silicon-carbon mixture as a negative electrode active material were prepared, respectively.

[0469] The negative electrode active material, Super-P as a conductive material, and polyacrylic acid were mixed with water at a weight ratio of 80:10:10, thereby preparing a negative electrode active material composition having a solid content of 45%.

[0470] The negative electrode active material composition was applied to a copper foil having a thickness of 18 μm and dried to prepare an electrode having a thickness of 70 μm. The copper foil coated with the electrode was punched into a circular shape having a diameter of 14 mm to prepare a negative electrode plate for a button cell.

[0471] Meanwhile, a metal lithium foil with a thickness of 0.3 mm was used as the positive electrode plate.

[0472] A porous polyethylene sheet with a thickness of 25 μm was used as a separator. A liquid electrolyte in which LiPF6 was dissolved in a mixed solvent of ethylene carbonate (EC) and diethylene carbonate (DEC) (volume ratio of 1:1) at a concentration of 1 M was used as an electrolyte. The above components were used to prepare a button cell (battery) with a thickness of 3.2 mm and a diameter of 20 mm.

[0473] Examples 2 to 12

[0474] A silicon-carbon mixture and a lithium secondary battery were prepared in the same manner as in Example 1, except that the types of the first composite material and the second composite material, their mixing weight ratio and O / Si molar ratio were changed, as shown in Table 5 below.

[0475] Comparative Example 1

[0476] A lithium secondary battery was prepared in the same manner as in Example 1, except that only the first composite material obtained in Preparation Example 3-1 was used without using the second composite material, as shown in Table 6 below.

[0477] Comparative Example 2

[0478] A lithium secondary battery was prepared in the same manner as in Example 1, except that only the second composite material obtained in Preparation Example 4-1 was used instead of the first composite material, as shown in Table 6 below.

[0479] Comparative Example 3

[0480] A silicon-carbon mixture and a lithium secondary battery were prepared in the same manner as in Example 1, except that the types of the first composite material and the second composite material, their mixing weight ratio and O / Si molar ratio were changed, as shown in Table 6 below.

[0481] <Test Example 1> X-ray Diffraction Analysis

[0482] Measurement of Si crystal size

[0483] The crystal size of Si in the first and second silicon particles in the silicon-carbon mixture was determined by the Scherrer equation of the following equation 3 based on the full width at half maximum (FWHM) of the peak corresponding to silicon (220) near 2θ=47.5° in the X-ray diffraction analysis.

[0484] [Equation 3]

[0485] Crystal size (nm) = Kλ / Bcosθ

[0486] In Equation 3, K is 0.9, λ is 0.154 nm, B is the full width at half maximum (FWHM), and θ is the peak position (angle).

[0487] Crystal structure of silicon-carbon mixture

[0488] The crystal structure of the silicon-carbon mixture prepared in the example was analyzed using an X-ray diffraction analyzer (X'Pert3 of Malvern Panalytical). Specifically, the applied voltage was 40 kV and the applied current was 40 mA. The range of 2θ was 10° to 80°, and the measurement was performed by scanning at intervals of 0.05°.

[0489] As a result of the analysis, it was confirmed that the silicon-carbon mixtures in the examples all had a peak corresponding to Si crystals, indicating that they contained crystalline Si, and peaks of MgSiO 3 and SiO 2 were also observed.

[0490] Specifically, from Figure 1It can be seen from the X-ray diffraction pattern that the silicon-carbon mixture of Example 1 has peaks corresponding to Si crystals near diffraction angles (2θ) of 28.6°, 47.5°, 56.2°, 69.3°, and 76.6°, indicating that crystalline Si is contained therein. In addition, diffraction angles (2θ) of MgSiO3 are observed at 30.4° and 35.6°. SiO2 is observed at 21.3°.

[0491] from Figure 2 It can be seen from the X-ray diffraction pattern that the silicon-carbon mixture of Example 7 has peaks corresponding to Si crystals near diffraction angles (2θ) of 28.5°, 47.3°, 56.2°, 69.2°, and 76.7°, indicating that crystalline Si is contained therein. In addition, the diffraction angles (2θ) of MgSiO3 are observed at 31.0° and 35.4°. SiO2 is observed at 21.3°.

[0492] <Test Example 2> Electron Microscope Analysis

[0493] The porous silicon composite material prepared in Preparation Example 2-1 was observed using an ion beam scanning electron microscope (FIB-SEM, focused ion beam system / Quanta 3D FEG) at magnifications of 10000, 30000 and 100000 times. The results are shown in Figures 3 to 5 .

[0494] In addition, the first composite material prepared in Preparation Example 3-1 was observed using a scanning electron microscope (FE-SEM, S-4700; Hitachi) at a magnification of 10,000 times. The results are shown in Figure 6 .

[0495] exist Figure 6 In FIG. 1 , bright white particles represent first silicon (Si) particles (crystals), and dark portions represent carbon (C).

[0496] In addition, the first composite material prepared in Preparation Example 3-1 was observed using a transmission electron microscope (FE-TEM, TECNAI G2 F20). The results are shown in Figure 7 and Figure 8 .

[0497] Figure 7 is a FE-TEM photograph of the first composite material prepared in Preparation Example 3-1. It shows the result of the bright field image. Figure 8 Results for dark-field and bright-field images are shown.

[0498] from Figure 7 and Figure 8 It can be seen that a carbon coating layer having a thickness of about 27±5 nm is formed on the surface of the first composite material.

[0499] <Test Example 3> Analysis of the content of constituent elements and density of composite materials

[0500] The contents of magnesium (Mg), oxygen (O), carbon (C) and silicon (Si) in the first composite material, the second composite material and the silicon-carbon mixture were analyzed.

[0501] The content of magnesium (Mg) was analyzed by inductively coupled plasma (ICP) emission spectrometry. The contents of oxygen (O) and carbon (C) were measured by an elemental analyzer. The content of silicon (Si) was calculated based on the contents of oxygen (O) and magnesium (Mg).

[0502] At the same time, the components contained in the silicon-carbon mixture were confirmed using FIB-SEM EDS (S-4700; Hitachi, QUANTA 3D FEG; FEI, EDS system; EDAX). As a result, the components Mg, C, O, and Si were observed in the silicon-carbon mixture.

[0503] Meanwhile, the density of the first composite material particles and the second composite material particles and the silicon-carbon mixture was measured using Acupick II1340 manufactured by Shimadzu Corporation after purging with helium 200 times on a sample holder set at a temperature of 23°C.

[0504] <Test Example 4> Measurement of average particle diameter of composite materials and composite material particles

[0505] The average particle diameter (D) of the first composite material particles, the second composite material particles, and the silicon-carbon mixture particles 50 ) is the average diameter D 50 The particle size is measured as the particle size or median diameter when the cumulative volume is 50% in the particle size distribution measurement according to the laser beam diffraction method.

[0506] <Test Example 5> Measurement of Capacity, Initial Efficiency and Capacity Retention Rate of Lithium Secondary Batteries

[0507] The single cells (lithium secondary batteries) prepared in the examples and comparative examples were each charged at a constant current of 0.1C until the voltage reached 0.005V, and then the current reached 0.005C at a constant voltage. Then, the charging capacity (mAh / g), the discharge capacity (mAh / g) and the initial efficiency (%) were measured at a constant current of 0.1C until the voltage reached 2.0V. The results are shown in Tables 5 and 6 below.

[0508] [Equation 4]

[0509] Initial efficiency (%) = discharge capacity / charge capacity × 100

[0510] In addition, the single cells (lithium secondary batteries) prepared in the examples and comparative examples were each charged at a constant current of 0.1 C until the voltage reached 4.25 V, and then the current reached 0.05 C at a constant voltage. Then, they were discharged at a constant current of 0.1 C until the voltage reached 2.5 V. 1000 cycles were performed under this condition, and the capacity retention rate after 1000 cycles was measured according to the following equation 5.

[0511] [Equation 5]

[0512] Capacity retention after 1000 cycles (%) = discharge capacity after 1000 cycles / discharge capacity at the first cycle × 100

[0513] The content of each element and the physical properties of the first composite material and the second composite material prepared in the preparation example are summarized in the following Tables 3 and 4, and the content of each element and the physical properties of the mixtures or composite materials prepared in the examples and comparative examples and the characteristics of the lithium secondary batteries using these mixtures or composite materials are summarized in the following Tables 5 to 7.

[0514] [Table 1]

[0515]

[0516] [Table 2]

[0517]

[0518]

[0519]

[0520] [Table 4]

[0521]

[0522]

[0523] [Table 6]

[0524]

[0525] [Table 7]

[0526]

[0527] It can be seen from Tables 5 to 7 above that in the lithium secondary batteries of Examples 1 to 12, the silicon-carbon mixture used includes a first composite material and a second composite material as two or more composite materials, containing silicon particles, magnesium silicate and carbon, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms satisfies a specific range. Compared with the lithium secondary batteries of Comparative Examples 1 to 3, when the discharge capacity, initial efficiency and capacity retention rate are comprehensively evaluated, all performances are improved.

[0528] Specifically, the silicon-carbon mixture used in the lithium secondary batteries of Examples 1 to 12 includes a first composite material and a second composite material and a molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms of 0.09 to 0.56, and in most cases the discharge capacity is about 1400 mAh / g or more, the initial efficiency is about 83% or more, and the capacity retention rate after 50 cycles is about 85% or more. In addition, the capacity retention rate of the lithium secondary batteries of Examples 10 to 12 after 1000 cycles is about 66% or more, indicating that the overall performance of the lithium secondary battery is excellent and the reliability is improved.

[0529] In contrast, in the lithium secondary battery of Comparative Example 1 (the silicon-carbon mixture used in the negative electrode active material only includes the first composite material and the molar ratio of oxygen (O) atoms to silicon (Si) atoms (O / Si) is 0.01), the capacity retention rate is 78.4%, and the capacity retention rate after 1000 cycles is 52%, which is significantly lower than that of the lithium secondary battery of the embodiment.

[0530] In addition, in the lithium secondary battery of Comparative Example 2 (the silicon-carbon mixture used in the negative electrode active material only includes the second composite material and the molar ratio of oxygen (O) atoms to silicon (Si) atoms (O / Si) is 0.98), the discharge capacity is about 1354 mAh / g, the initial efficiency is 81%, and the capacity retention rate after 1000 cycles is 57%, which is significantly reduced compared with the lithium secondary battery of the embodiment.

[0531] At the same time, in the lithium secondary battery of Comparative Example 3 (the silicon-carbon mixture used includes a first composite material and a second composite material and the molar ratio of oxygen (O) atoms to silicon (Si) atoms (O / Si) is 0.91), the discharge capacity is 1368 mAh / g, the initial efficiency is 82.1%, and the capacity retention rate after 1000 cycles is about 54%, which is significantly reduced compared with the lithium secondary battery of the embodiment.

[0532] Meanwhile, when the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms is less than 0.06, manufacturing cannot be performed.

[0533] In addition, according to the embodiment, since the carbon content and porosity can be easily controlled, excellent capacity retention can be maintained even after thousands of cycles or more for a long period of time, while satisfying the above-mentioned molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon mixture, which can further improve reliability.

Claims

1. A silicon-carbon mixture comprising two or more types of composite materials, comprising silicon particles, magnesium silicate and carbon, and having a molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms of 0.06 to 0.

90.

2. The silicon-carbon mixture according to claim 1, wherein: The two or more types of composite materials include a first composite material and a second composite material, The first composite material comprises first silicon particles and first carbon, and The second composite material includes second silicon particles, magnesium silicate, and second carbon.

3. The silicon-carbon mixture according to claim 2, wherein: The molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the first composite material is 0.005 to 0.50, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the second composite material is 0.8 to 1.

2.

4. The silicon-carbon mixture according to claim 2, wherein: The weight ratio of the first composite material to the second composite material is 90:10 to 5:

95.

5. The silicon-carbon mixture according to claim 1, wherein: The silicon-carbon mixture includes silicon aggregates in which silicon particles are combined with each other, and the magnesium silicate includes MgSiO3, Mg2SiO4 or a mixture thereof.

6. The silicon-carbon mixture according to claim 1, wherein: In the silicon-carbon mixture, based on the total weight of the silicon-carbon mixture, The content of oxygen (O) is 1 wt% to 25 wt%, The content of silicon (Si) is 35 wt % to 80 wt %, The content of magnesium (Mg) is 0.1 wt % to 15 wt %, and The content of carbon (C) is 9 wt% to 50 wt%, and The molar ratio (Mg / Si) of magnesium (Mg) atoms to silicon (Si) atoms in the silicon-carbon mixture is 0.009 to 0.

55.

7. The silicon-carbon mixture according to claim 1, wherein: The silicon-carbon mixture further comprises silicon oxide (SiO x , 0.4 <x≤2)。 8. The silicon-carbon mixture according to claim 2, wherein: The first composite material includes a silicon composite material and a first carbon layer on the surface thereof, first silicon particles are present in the silicon composite material, and first carbon is contained in the first carbon layer and inside the silicon composite material, and The second composite material includes a silicon composite oxide and a second carbon layer on the surface thereof, second silicon particles and magnesium silicate are present in the silicon composite oxide, and the second carbon is contained in at least one selected from the second carbon layer, the surface of the second silicon particle, and the surface of the second magnesium silicate.

9. The silicon-carbon mixture according to claim 2, wherein: The content of oxygen (O) in the first composite material is 0.1 wt % to 16 wt % based on the total weight of the first composite material, and The content of oxygen (O) in the second composite material is 20 wt % to 40 wt % based on the total weight of the second composite material.

10. The silicon-carbon mixture according to claim 2, wherein: The content of carbon (C) in the first composite material is 10 wt % to 50 wt % based on the total weight of the first composite material, and The content of carbon (C) in the second composite material is 3 wt % to 15 wt % based on the total weight of the second composite material.

11. A method for preparing the silicon-carbon mixture according to claim 1, the method comprising: A first step of obtaining a first composite material; A second step of obtaining a second composite material; as well as a third step of mixing the first composite material and the second composite material, The first composite material comprises first silicon particles and first carbon, and the second composite material comprises second silicon particles, magnesium silicate, and second carbon.

12. The method for preparing a silicon-carbon mixture according to claim 11, wherein: The first step of obtaining the first composite material comprises: a first-first step of etching the first silicon-based raw material powder using an etching solution, the etching solution containing a compound containing fluorine (F) atoms; The first-second steps of filtering and drying the product obtained by etching to obtain a silicon composite material; and The first to third steps are to form first carbon inside the silicon composite material and a first carbon layer on the surface of the silicon composite material using a chemical thermal decomposition deposition method to obtain a first composite material.

13. The method for preparing a silicon-carbon mixture according to claim 11, wherein: The second step for preparing the second composite material comprises: a second-first step of obtaining a silicon composite oxide using a second silicon-based raw material and a magnesium-based raw material; A second-second step of pulverizing and / or classifying the silicon composite oxide to obtain a silicon composite oxide powder; and The second to third steps are to form a second carbon layer on the surface of the silicon composite oxide powder using a chemical thermal decomposition deposition method to obtain a second composite material. 14 . A negative electrode active material comprising the silicon-carbon mixture according to claim 1 . 15 . A lithium secondary battery comprising the negative electrode active material according to claim 14 .

Citation Information

Patent Citations

  • Porous silicon-based negative electrode active material and lithium secondary battery containing the same

    JP2016502253A